Composite particles comprising a hydrophobic dye and an amphiphilic block copolymer and their use in optical applications

Encapsulating hydrophobic dyes with amphiphilic block copolymers in composite particles addresses dye migration and stability issues, ensuring effective light filtering in contact lenses by maintaining optical properties and safety.

CN114207050BActive Publication Date: 2024-12-13COLOURSMITH LABS INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202080053222.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-05-24
Filing Date
2020-05-25
Publication Date
2024-12-13
Estimated Expiration
2040-05-25

AI Technical Summary

Technical Problem

Current methods for incorporating dyes into contact lenses face challenges such as dye migration, loss of optical properties, and health risks due to dye release, particularly with dyes like Zn(II)TPP, which lack appropriate chemical functionality for direct covalent attachment to hydrogel materials, and are degraded by UV/HEV light during lens manufacturing.

Method used

Composite particles comprising hydrophobic dyes encapsulated by amphiphilic block copolymers, formed through methods involving dye/polymer solutions in organic solvents mixed with water to create aqueous micellar solutions, which are then filtered to obtain stable particles suitable for contact lenses.

Benefits of technology

The encapsulation method maintains the dyes' optical properties and stability under harsh manufacturing conditions, reducing migration and health risks, while allowing for effective light filtering in contact lenses.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003484935250000311
    Figure BDA0003484935250000311
  • Figure BDA0003484935250000312
    Figure BDA0003484935250000312
  • Figure BDA0003484935250000361
    Figure BDA0003484935250000361
Patent Text Reader

Abstract

Composite particles of amphiphilic block copolymers comprising hydrophobic dyes and encapsulated dyes are disclosed. The dyes show absorption peaks at one or more points in the ultraviolet, visible or infrared regions of the electromagnetic spectrum. Therefore, the particles are useful in optical applications (e.g., the preparation of contact lenses that can shield harmful radiation). In a selected embodiment, the dye is zinc (II) 5,10,15,20-(tetraphenyl) porphyrin and the copolymer is a cross-linked acrylate or PEO copolymer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to composite particles comprising one or more hydrophobic dyes and one or more amphiphilic block copolymers, and to compositions comprising such composite particles, and their uses, such as selective light filtering, optionally in contact lenses, including hydrogel-based contact lenses and silicone hydrogel-based contact lenses. The present disclosure also relates to eyeglass lenses comprising one or more composite particles or one or more compositions of the present disclosure. Background Art

[0002] Optical filters are devices with wavelength selective transmission acting on light sources or light receivers. Such optical filters can be configured to transform aspects of the color appearance seen by the human eye or any recording device. Optical filters are useful, for example, in situations where light of a specific wavelength must be controlled, adjusted or attenuated, especially in fields including but not limited to vision care, medical treatment, eyeglass lens development, film photography and entertainment. For example, the optical filter in the eyeglass lens can provide eye protection from high-energy radiation in the ultraviolet (UV) spectrum, visible spectrum and / or infrared spectrum. Optical filters can also provide cosmetic benefits, such as color balance to improve the beauty of contact lenses or enhance the visual effects required for entertainment colors or realization. In addition, optical filters can be used in medical applications of eyeglass lenses, such as changing the spectral response of people associated with short (S), medium (M) and long (L) cone photoreceptors, for treating hereditary and / or non-hereditary vision conditions such as color vision defects or myopia.

[0003] Currently, there are two different methods for preparing filter contact lenses containing filter additives (e.g., dyes). The first method is to incorporate one or more dyes into the contact lens by soaking the hydrated or non-hydrated lens in a bath of one or more dyes and solvents. This method may result in the migration of dye molecules from the bulk, hydrogel material, loss or reduction of filter ability, and possible health problems due to the release of one or more dyes to the eye.

[0004] The second method is to directly cure the contact lens monomer solution containing dye to incorporate one or more dyes into the contact lens, wherein the dye is particularly functionalized to be reactive to the contact lens monomer. For example, the dye can be functionalized with a vinyl sulfonyl group or a halogen triazine group. Although attempts to polymerize one or more dyes with hydrogel monomers can significantly reduce the migration of dye molecules from the main hydrogel material, only a limited number of commercially valuable dyes have the appropriate local chemical composition required for covalently connecting with the main hydrogel material. Applying this method to non-functionalized dyes will usually require careful redesign and dye modification to have the appropriate local chemical composition to meet the covalent connection in the main hydrogel material. Further, synthetically changing the non-functionalized dye in this way may cause changes in the dye's natural absorption spectrum, making it unsuitable for use as a filter for a desired application, and the dye is selected just because of the desired application.

[0005] For example, the light absorbing dye zinc(II)tetraphenylporphyrin (Zn(II)TPP) has optical properties that make it commercially valuable as a HEV / blue light blocker in contact lenses. However, Zn(II)TPP does not have the appropriate topical chemistry required for direct covalent attachment to a bulk hydrogel material. Synthetically modifying Zn(II)TPP to provide the correct functionalization results in loss, reduction, and / or alteration of its HEV / blue light blocking ability.

[0006] Depending on the particular set of light absorbing additives used therein, different challenges arise from the process necessitating the various properties of the dyes used.

[0007] For example, the one or more dyes to be incorporated into the contact lens monomers may be exposed to a number of harsh lens manufacturing processes and conditions, such as photocuring by UV / HEV light, thermal curing by application of heat, and / or catalytic polymerization initiated by incorporation of a polymerization catalyst into the bulk contact lens monomers. In addition, during use, contact lenses containing one or more dyes may be exposed to damaging UV / HEV radiation from natural and / or artificial sources.

[0008] The manufacture of hydrogel-based contact lenses typically uses photocuring through the use of UV / HEV light, which degrades the optical properties of the dyes, rendering many dyes unusable for light filtering applications in contact lenses.

[0009] Additionally, during the lens manufacturing process, dyes may be exposed to various organic solvent extractions, solvent washing, hydration, autoclave sterilization, and / or prolonged exposure to high or low temperatures. One of the solvents used in the contact lens manufacturing process is ethanol. Summary of the invention

[0010] The present disclosure relates to composite particles, compositions comprising such composite particles and methods of preparing the same. The present disclosure also relates to their use as filters in contact lenses, and methods of filtering light in contact lenses. The present disclosure further relates to contact lenses comprising the composite particles or compositions thereof.

[0011] Thus, in one aspect, the present disclosure includes a composite particle comprising:

[0012] hydrophobic dyes; and

[0013] Amphiphilic block copolymers encapsulating hydrophobic dyes,

[0014] The hydrophobic dyes have absorbance in the range from the ultraviolet region to the infrared region of the electromagnetic spectrum.

[0015] In another aspect, the present disclosure includes a composition comprising the composite particles of the present disclosure in a solvent selected from the group consisting of an aqueous solvent, an organic solvent, and combinations thereof.

[0016] In another aspect, the present disclosure includes a contact lens comprising one or more composite particles or compositions of the present disclosure.

[0017] In another aspect, the present disclosure includes composite particles or compositions of the present disclosure for use as an optical filter, optionally in a contact lens, optionally wherein the contact lens is hydrogel-based or silicone hydrogel-based.

[0018] In another aspect, the present disclosure includes the use of one or more composite particles or compositions of the present disclosure as an optical filter, optionally as an optical filter in a contact lens.

[0019] In another aspect, the present disclosure includes a method of filtering light comprising selectively blocking optical radiation using one or more composite particles or compositions of the present disclosure.

[0020] In another aspect, the present disclosure includes a method of preparing a composition of the present disclosure, comprising:

[0021] preparing a dye / polymer solution comprising a hydrophobic dye and an amphiphilic block copolymer in an organic solvent; and

[0022] The dye / polymer solution is added to water with mixing to obtain the composition in the form of an aqueous micellar solution.

[0023] In another aspect, the present disclosure includes a method of preparing a composition of the present disclosure in the form of an aqueous solution, the composition including the composite particles of the present disclosure, the method comprising:

[0024] preparing a dye / polymer / crosslinker solution comprising a hydrophobic dye, an amphiphilic block copolymer, and one or more crosslinkers in an organic solvent;

[0025] The dye / polymer / crosslinker solution is added to water with mixing to obtain an aqueous micellar solution.

[0026] A method for preparing the composite particles of the present disclosure comprises:

[0027] preparing a dye / polymer solution comprising a hydrophobic dye and an amphiphilic block copolymer in an organic solvent;

[0028] adding the dye / polymer solution to water while stirring to obtain composite particles in aqueous solution; and

[0029] The composite particles are optionally obtained from the aqueous solution by filtration.

[0030] A method for preparing the composite particles of the present disclosure comprises

[0031] preparing a dye / polymer / cross-linker solution comprising a hydrophobic dye, an amphiphilic block copolymer, and a cross-linker in an organic solvent;

[0032] adding the dye / polymer / crosslinker solution to water while stirring to obtain an aqueous solution; and

[0033] The composite particles are optionally obtained from the aqueous solution by filtration.

[0034] Other features and advantages of the present disclosure will become apparent from the following detailed description. However, it should be understood that the detailed description and specific examples, although describing the embodiments of the present application, are only given by way of example, and the scope of the claims should not be limited to these embodiments, but should be given the broadest interpretation consistent with the entire description. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Embodiments of the present application will now be described in more detail with reference to the accompanying drawings, in which:

[0036] Figure 1 An illustrative schematic diagram of a packaging process according to an embodiment of the present disclosure is shown.

[0037] Figure 2 The dye Epolight is shown without encapsulation and with encapsulation. TM Comparison of UV-Vis absorption spectra of 5843.

[0038] Figure 3 shows the Epolight dye without encapsulation and encapsulation TM Physical appearance of 5843. Panel A shows the dye, which is not encapsulated and is insoluble in water. Panel B shows the dye dissolved in tetrahydrofuran (THF). Panel C shows an exemplary image of the encapsulated dye in an aqueous medium.

[0039] Figure 4 shows spectral data and physical appearance of a composite particle composition containing the dye Exciton ABS 594 according to one embodiment of the present disclosure. Panel A shows a comparison between UV-Vis absorption spectra of unencapsulated and encapsulated dyes. Panel B shows a calibration curve of the encapsulated dye in 10% THF and 90% water.

[0040] Figure 5 shows spectral data and physical appearance of a composite particle composition containing the dye Exciton ABS 456 according to one embodiment of the present disclosure. Panel A shows a comparison between UV-Vis absorption spectra of unencapsulated and encapsulated dyes. Panel B shows a calibration curve of the encapsulated dye in 10% THF and 90% water.

[0041] FIG6 shows exemplary transmission electron microscopy (TEM) images and dynamic light scattering (DLS) results of composite particles containing dye Exciton ABS 594 according to one embodiment of the present disclosure. FIGA shows a TEM image of composite particles containing dye Exciton ABS 594. The scale bar represents 100 nm. FIGB shows DLS results of composite particles containing dye Exciton ABS 594.

[0042] FIG7 shows exemplary TEM images and DLS results of composite particles containing dye Exciton ABS 456 according to one embodiment of the present disclosure. FIG. A shows a TEM image of composite particles containing dye Exciton ABS 456. The scale bar represents 200 nm. FIG. B shows DLS results of composite particles containing dye Exciton ABS 456.

[0043] Figure 8 Shown is the UV-Vis absorption spectrum of a composition of Exciton ABS 594 composite particles and Exciton ABS 456 composite particles according to one embodiment of the present invention.

[0044] Figure 9 shows UV-Vis absorption spectra of composite particle compositions formed using General Encapsulation Procedures 1, 2, and 3 according to embodiments of the present disclosure. Panel A shows a comparison between free dye and composite particle compositions formed using a syringe pump (General Encapsulation Procedure 2). Panel B shows a comparison between composite particle compositions formed using a syringe pump (General Encapsulation Procedure 2) and a Pasteur pipette (General Encapsulation Procedure 1). Panel C shows a comparison between composite particle compositions formed using a syringe pump (General Encapsulation Procedure 2) and FNPs (General Encapsulation Procedure 3).

[0045] Fig.10Shown are overlays of UV-Vis spectra of Exciton ABS 456 composite particle compositions at different time points (1 day, 1 week, 3 weeks, 7 weeks, and 11 weeks) according to embodiments of the present disclosure.

[0046] Figure 11 shows the results of UV stability testing for Exciton ABS 456 composite particle compositions and free dye according to one embodiment of the present invention. Panel A shows a comparison between the UV-Vis absorption spectra of the free dye before and after UV exposure for different lengths of time (10 minutes, 20 minutes or 30 minutes). Panel B shows a comparison between the UV-Vis absorption spectra of the composite particles before and after UV exposure.

[0047] FIG. 12 shows DLS results of an Exciton ABS 456 composite particle composition before and after UV exposure according to one embodiment of the present disclosure. FIG. A and FIG. B show the number distribution and intensity distribution of the composite particle composition before UV exposure, respectively. FIG. C and FIG. D show the number distribution and intensity distribution of the composite particle composition after UV exposure, respectively. FIG. E and FIG. F show scanning electron microscope (SEM) images of the composite particles before and after UV exposure, respectively. The scale bar in each SEM represents 5 μm.

[0048] Fig.13 Shown is a comparison of UV-Vis spectra of an Exciton ABS 456 composite particle composition before and after heating according to one embodiment of the present disclosure.

[0049] Fig.14 Shown are the absorption spectra of an Exciton ABS 594 composite particle composition before and after heating according to one embodiment of the present disclosure.

[0050] Figure 15 shows UV-Vis spectra of Exciton ABS 456 composite particle compositions in different concentrations of THF / water at different time points and after UV bleaching according to one embodiment of the present disclosure. Panel A shows the UV-Vis spectra of the composite particle composition in 35% v / v THF followed by UV exposure for different lengths of time. Panel B shows the UV-Vis spectra of the composite particle composition in 10% v / v THF followed by UV exposure for different lengths of time. Panel C shows the UV-Vis spectra of the composite particle composition in 64% v / v THF followed by UV exposure for different lengths of time. Panel D shows the UV-Vis spectra of the composite particle composition in 99% v / v THF followed by UV exposure for different lengths of time.

[0051] Fig.16Shown is an optical image of a polyacrylamide gel doped with ABS 594 and ABS 456 encapsulated dye micelles according to one embodiment of the present disclosure.

[0052] Fig.17 Shown is the absorption spectrum of a polyacrylamide gel doped with ABS 594 and ABS 456 encapsulated dye micelles according to one embodiment of the present disclosure.

[0053] Fig.18 Shown are the UV-Vis absorption spectra of composite particles prepared using direct injection (A), flash nanoprecipitation (B), ultrasound method (C), and vortex method (D).

[0054] Fig.19 Shown are the UV-Vis absorbances of the amphiphilic block copolymer, free dye and dye + amphiphilic block copolymer after flocculation with calcium chloride.

[0055] Fig. 20 TEM images of composite particles containing the following different dyes are shown: 1,3,5,7-tetramethyl-8-(4-hydroxyphenyl) BODIPY (A); 1,7-(di-4,N,N-dimethylaminophenyl)-3,5-(di-4-bromophenyl) AZABODIPY (B); 2,3,7,8,12,13,17,18-(octabromo)-5,10,15,20-(tetraphenyl) porphyrin (C); zinc (II) 2,9,16,23-(tetranitro) phthalocyanine (D); coumarin 153 (E); vitamin E (F); β-carotene (G); perylene (H); p-quaterphenyl (I); and vanadyl 2,3-naphthalocyanine (J); 2-[3-(2H-benzotriazol-2-yl)-4-hydroxy-phenyl]ethyl methacrylate (NORBLOC TM )(K).

[0056] Fig.21 The UV-Vis absorbance of composite particles containing the following different dyes is shown: 1,3,5,7-tetramethyl-8-(4-hydroxyphenyl) BODIPY (A); 1,7-(di-4,N,N-dimethylaminophenyl)-3,5-(di-4-bromophenyl) AZABODIPY (B); 2,3,7,8,12,13,17,18-(octabromo)-5,10,15,20-(tetraphenyl) porphyrin (C); zinc (II) 2,9,16,23-(tetranitro) phthalocyanine (D); coumarin 153 (E); vitamin E (F); β-carotene (G); perylene (H); p-quaterphenyl (I); and vanadyl 2,3-naphthalocyanine (J); 2-[3-(2H-benzotriazol-2-yl)-4-hydroxy-phenyl]ethyl methacrylate (NORBLOCTM )(K).

[0057] Fig. 22 Figure 29 shows the 29Si solid-state NMR spectra of TEOS cross-linked composite particles containing zinc(II) 5,10,15,20-(tetraphenyl)porphyrin. Figure A shows the cross-linking of poly(styrene) using TEOS 1300 -b-Poly(ethylene oxide) 5600 Figure B shows the spectrum of poly(1,2-butadiene) cross-linked with TEOS 15000 -b-Poly(acrylic acid) 6500 Figure C shows the spectrum of poly(1,2-butadiene) cross-linked with TEOS 31500 -b-Poly(methyl methacrylate) 21000 Panel D shows the spectrum of the control sample.

[0058] Fig.23 SEM and TEM images of the following composite particles crosslinked with TEOS are shown: poly(1,2-butadiene) crosslinked with 1x, 2x or 5x TEOS by weight compared to the weight of the hydrophilic polymer block 15000 -b-Poly(acrylic acid) 6500 (left to right in Figure A); poly(1,2-butadiene) crosslinked using 1x, 2x or 5x TEOS by weight compared to the weight of the hydrophilic polymer block 31500 -b-Poly(methyl methacrylate) 21000 (left to right in Figure B); poly(styrene) cross-linked using 1x, 2x or 5x TEOS by weight compared to the weight of the hydrophilic polymer block 1300 -b-Poly(ethylene oxide) 5600 (left to right in Figure C); and poly(vinyl alcohol) crosslinked using 1x, 2x or 5x TEOS by weight compared to the weight of the hydrophilic polymer block 2300 -b-Poly(methyl methacrylate) 25000 (From left to right in Figure D).

[0059] Fig.24 Composite particles of poly(1,2-butadiene) with zinc(II) 5,10,15,20-(tetraphenyl)porphyrin freeze-dried with the cryoprotectant PEG 4000 are shown. 31500 -b-PMMA 21000 UV-Vis absorbance.

[0060] Fig.25 Shown are the UV-Vis absorption spectra of various composite particles in M2Dx prepolymer solutions.

[0061] Fig.26 Representative photographs of polymerized M2Dx gels containing composite particles of the present disclosure are shown.

[0062] Fig. 27 Shown are the UV-Vis absorbance of M2Dx polymer gels containing different composite particles (CS28 to CS42), comparative particles (BC01, PH01, PN01) and control particles (CS00).

[0063] Fig.28 Shown on the left side of each figure are the UV-Vis absorbance of M2Dx polymer gels containing CS34 (A), CS37 (B), CS41 (C) or CS42 (D) composite particles after 95% ethanol extraction, and on the right side of each figure are the corresponding UV-Vis absorption spectra of 95% ethanol washes.

[0064] Fig.29 Representative UV-Vis absorption spectra of autoclaved M2Dx polymer gels containing different composite particles are shown. Gels containing CS38, CS39, CS40 and CS41 are shown as examples.

[0065] Fig.30 Shown is the post-autoclaving UV-Vis absorbance of autoclaved saline containing different composite particles of M2Dx polymer gel.

[0066] Fig.31 The UV-Vis absorbance of the composite particles after exposure to different solvents is shown. Figures A to F show the composite particles PN01, CS19, CS29, CS31, CS33 and CS34 after exposure to ethanol. Figures G to I show the UV-Vis absorption spectra of the composite particles CS20, CS22 and CS04 after exposure to different solvents, respectively.

[0067] Fig.32 Representative UV-Vis absorbance of M2Dx polymer gels containing composite particles CS35 after photobleaching for 1 minute, 2 minutes, 3 minutes, 4 minutes, or 5 minutes are shown.

[0068] Fig.33 Shown are the UV-Vis absorption spectra of saline after photoaging of M2Dx polymer gels containing different composite particles in saline. DETAILED DESCRIPTION

[0069] I. Definitions

[0070] Unless otherwise stated, the definitions and examples described in this section and elsewhere are intended to apply to all embodiments and aspects of the disclosure described herein, as those skilled in the art will understand that they are suitable for these embodiments and aspects.

[0071] As used in this disclosure, the singular form "a," "an," and "the" include plural references unless the context clearly dictates otherwise.

[0072] The terms "about", "substantially" and "approximately" as used herein refer to a reasonable amount of deviation of the modified term so that the end result is not significantly changed. If this deviation does not negate the meaning of the word it modifies, or unless the context suggests otherwise to a person skilled in the art, the extent of these terms should be interpreted as including a deviation of at least ±5% of the modified term.

[0073] This description involves many chemical terms and abbreviations used by those skilled in the art. Nevertheless, for the sake of clarity and consistency, definitions of selected terms are provided.

[0074] As used herein, the term "hydrophobic", such as in "hydrophobic dye", refers to the property of a molecule or portion thereof that is not attracted to water molecules. For example, it includes repelling or tending not to bind to water, or not being completely soluble in water. For example, when referring to a hydrophobic dye, the term hydrophobic can mean that the dye is substantially insoluble in water, but soluble in a water-soluble organic solvent.

[0075] The term "hydrophilic," as used herein, refers to the property of a molecule or portion thereof being attracted to water molecules.

[0076] As used herein, the term "optionally substituted" refers to a group, structure or molecule that is unsubstituted or substituted with one or more substituents.

[0077] As used herein, the term "amphiphilic copolymer" refers to a copolymer comprising subunits or monomers having different hydrophobic or hydrophilic properties. For example, when subunits or monomers of the same properties are present in blocks in the same copolymer chain, the copolymer is referred to as a block copolymer. For example, an amphiphilic block copolymer comprises blocks wherein one or more blocks comprise one or more types of hydrophilic subunits or monomers, while other blocks comprise one or more types of hydrophobic subunits or monomers, such that each block is substantially hydrophilic or hydrophobic. It is possible for one or more types of hydrophilic or hydrophobic subunits or monomers to be dispersed throughout the copolymer but still produce substantially generally hydrophilic or hydrophobic blocks.

[0078] The term "hydrogel" as used herein refers to a gel in which the swelling agent is water. In some embodiments, it refers to a gel comprising a polymer network material having an equilibrium water content of at least 10% w / w. A hydrogel comprising a silicone component is referred to herein as a "silicone hydrogel".

[0079] As used herein, the term "blue light" refers to the high-energy blue portion of the spectrum. For example, it may refer to the portion of the spectrum ranging from about 380 nm to 500 nm.

[0080] As used herein, the term "selectively blocks light" and the like means providing minimal transmission in a selected portion of the light spectrum.

[0081] II. Composite particles, compositions and uses thereof

[0082] In one aspect, the present disclosure includes a composite particle comprising:

[0083] hydrophobic dyes; and

[0084] Amphiphilic block copolymers encapsulating hydrophobic dyes,

[0085] The hydrophobic dyes have absorbance in the range from the ultraviolet region to the infrared region of the electromagnetic spectrum.

[0086] In some embodiments, the amphiphilic block copolymer is cross-linked, for example, by one or more cross-linking agents.

[0087] In some embodiments, the composite particles are synthetic polymer micelles.

[0088] The hydrophobic dye is any suitable hydrophobic dye having absorbance in the range of the ultraviolet region to the infrared region of the electromagnetic spectrum. In some embodiments, the hydrophobic dye is a laser dye or an absorbing dye. In one embodiment, the hydrophobic dye is a laser dye. Those skilled in the art will appreciate that laser dye solutions absorb at shorter wavelengths and emit at longer wavelengths. In another embodiment of the present disclosure, the hydrophobic dye is an absorbing dye.

[0089] In some embodiments, the hydrophobic dye is selected from coumarins, fluoresceins, rhodamines, pyrromethenes, cyanines, carbocyanines, flavins, oxazines, carbazines, stilbenes, diphenylstilbenes, oxazoles, biphenyls, terphenyls, quaterphenyls, polyphenyls, phenyloxazones, phenoxazoniums, pyridines, pyridiniums, carotenoids. In some embodiments, the hydrophobic dye is selected from BODIPY, AzaBODIPY, tetraphenylporphyrin, phthalocyanine, naphthalocyanine, coumarin, benzotriazole, tocopherol, tocotrienol, carotenoid, anthracene, perylene, polycyclic aromatic hydrocarbons (PAH), polyene, corrin, chlorin, corphine, indolenine, chlorophyll, azo dye, polymethine, diarylmethane, triarylmethane, polyene, anthracenedione, pyrazolone, anthraquinone, pyran, phenothiazine, triazine, oxalanilide, acridine, benzanthrone and combinations thereof. In some embodiments, the hydrophobic dye is selected from BODIPY, AzaBODIPY, tetraphenylporphyrin, phthalocyanine, naphthalocyanine, coumarin, benzotriazole, tocopherol, tocotrienol, carotenoid, anthracene, perylene, metal oxides and combinations thereof. In some embodiments, the hydrophobic dye is selected from 1,3,5,7-tetramethyl-8-(4-hydroxyphenyl) BODIPY, 1,7-(di-4-N,N-dimethylaminophenyl)-3,5-(di-4-bromophenyl) AZABODIPY, 2,3,7,8,12,13,17,18-(octabromo)-5,10,15,20-(tetraphenyl) porphyrin, Zn(II) 5,10,15,2 0-tetraphenyl-21H, 23H-porphyrin (Zn(II)TPP), Zn(II)2,9,16,23-(tetranitro)phthalocyanine, coumarin 153, 2-(2'hydroxy-5'-methacryloyloxyethylphenyl)-2H-benzotriazole, vitamin E, β-carotene, 9,10-diphenylanthracene, perylene, chromium (III) oxide, p-quaterphenyl, vanadyl 2,3-naphthalocyanine and combinations thereof. In some embodiments, the hydrophobic dye is Zn(II)5,10,15,20-tetraphenyl-21H, 23H-porphyrin (Zn(II)TPP).

[0090] The amphiphilic block copolymer is any suitable amphiphilic block copolymer that encapsulates a hydrophobic dye. In some embodiments, the amphiphilic block copolymer is a copolymer based on poly(alkyl acrylate), a copolymer based on poly(alkyl methacrylate), a copolymer based on poly(acrylic acid), a copolymer based on poly(methacrylic acid), a copolymer based on poly(diene), a copolymer based on poly(N-isopropylacrylamide), a copolymer based on poly(ethylene glycol), a copolymer based on poly(methylene indan), a copolymer based on poly(siloxane), a copolymer based on poly(styrene), a copolymer based on substituted poly(styrene), a copolymer based on poly(vinylpyridine), a copolymer based on poly(vinyl alcohol), a copolymer based on poly(alkyl acrylic acid), a copolymer based on poly(alkylene oxide), a copolymer based on poly(dialkylsiloxane), a copolymer based on poly(olefin), a copolymer based on poly(alkylene oxide diacrylate), a copolymer based on poly(butylene glycol diacrylate), or a combination thereof. In some embodiments, the amphiphilic block copolymer is a poly(alkyl acrylate)-based copolymer, a poly(alkyl methacrylate)-based copolymer, a poly(acrylic acid)-based copolymer, a poly(methacrylic acid)-based copolymer, a poly(diene)-based copolymer, a poly(olefin)-based copolymer, a poly(ethylene glycol)-based copolymer, a poly(siloxane)-based copolymer, a poly(styrene)-based copolymer, a poly(vinyl alcohol)-based copolymer, a poly(dialkylsiloxane)-based copolymer, or a combination thereof. In some embodiments, the amphiphilic block copolymer is a poly(methyl acrylate)-based copolymer, a poly(n-butyl acrylate)-based copolymer, a poly(methyl methacrylate)-based copolymer, a poly(tert-butyl methacrylate)-based copolymer, a poly(acrylic acid)-based copolymer, a poly(methacrylic acid)-based copolymer, a poly(1,2-butadiene)-based copolymer, a poly(1,4-butadiene)-based copolymer, a poly(styrene)-based copolymer, a poly(dimethylsiloxane)-based copolymer, a poly(vinyl alcohol)-based copolymer, a poly(propylene oxide)-based copolymer, or a combination thereof.

[0091] In some embodiments, the amphiphilic block copolymer is a diblock copolymer or a triblock copolymer, or a combination thereof. In some embodiments, the amphiphilic block copolymer is a diblock copolymer. In some embodiments, the amphiphilic block copolymer is poly(ethylene glycol)-b-poly(styrene), poly(n-butyl acrylate)-b-poly(acrylic acid), or poly(methyl methacrylate)-b-poly(methacrylic acid).In some embodiments, the amphiphilic block copolymer is selected from the group consisting of poly(1,2-butadiene)-b-poly(acrylic acid), poly(1,2-butadiene)-b-poly(ethylene oxide), poly(1,2-butadiene)-b-poly(methacrylic acid), poly(1,2-butadiene)-b-poly(methyl methacrylate), poly(1,2-butadiene)-b-poly(vinyl alcohol), poly(1,2-butadiene-co-1,4-butadiene)-b-poly(acrylic acid), poly(1,2-butadiene-co-1,4-butadiene)-b-poly(ethylene oxide), poly(1,2-butadiene-co-1,4-butadiene)-b-poly(methacrylic acid), poly(1,2 -butadiene-co-1,4-butadiene)-b-poly(vinyl alcohol), poly(1,4-butadiene)-b-poly(acrylic acid), poly(1,4-butadiene)-b-poly(ethylene oxide), poly(1,4-butadiene)-b-poly(methacrylic acid), poly(1,4-butadiene)-b-poly(vinyl alcohol), poly(dimethylsiloxane)-b-poly(acrylic acid), poly(dimethylsiloxane)-b-poly(ethylene oxide), poly(dimethylsiloxane)-b-poly(methacrylic acid), poly(dimethylsiloxane)-b-poly(n-butyl acrylate), poly(ethylene oxide)-b-poly(butadiene), poly(ethylene oxide)-b-poly(dimethylsiloxane) alkyl), poly(ethylene oxide)-b-poly(methyl methacrylate), poly(ethylene oxide)-b-poly(n-butyl acrylate), poly(ethylene oxide)-b-poly(styrene), poly(ethylene oxide)-b-poly(tert-butyl methacrylate), poly(methyl methacrylate)-b-poly(acrylic acid), poly(methyl methacrylate)-b-poly(dimethylsiloxane), poly(methyl methacrylate)-b-poly(ethylene oxide), poly(methyl methacrylate)-b-poly(methacrylic acid), poly(methyl methacrylate)-b-poly(styrene), poly(n-butyl acrylate)-b-poly(acrylic acid), poly(propylene oxide)-b-poly(butadiene ), poly(propylene oxide)-b-poly(dimethylsiloxane), poly(propylene oxide)-b-poly(methyl methacrylate), poly(propylene oxide)-b-poly(n-butyl acrylate), poly(propylene oxide)-b-poly(styrene), poly(propylene oxide)-b-poly(tert-butyl methacrylate), poly(vinyl alcohol)-b-poly(butadiene), poly(vinyl alcohol)-b-poly(dimethylsiloxane), poly(vinyl alcohol)-b-poly(methyl methacrylate), poly(vinyl alcohol)-b-poly(n-butyl acrylate), poly(vinyl alcohol)-b-poly(styrene), poly(vinyl alcohol)-b-poly(tert-butyl methacrylate), poly(1,2-butadiene). 15000 -b-Poly(acrylic acid) 6500 , poly(1,4-butadiene) 9000 -b-Poly(acrylic acid) 3500 , poly(dimethylsiloxane) 5000-b-Poly(ethylene oxide) 2100 , poly(dimethylsiloxane) 8000 -b-Poly(acrylic acid) 8000 , poly(methyl methacrylate) 3000 -b-Poly(ethylene oxide) 3000 , poly(methyl methacrylate) 7400 -b-Poly(acrylic acid) 24300 , Poly(n-butyl acrylate) 7500 -b-Poly(acrylic acid) 5500 , poly(styrene) 1300 -b-Poly(ethylene oxide) 5600 , poly(vinyl alcohol) 2300 -b-Poly(methyl methacrylate) 25000 , poly(vinyl alcohol) 2500 -b-Poly(styrene) 12500 , and their combinations.

[0092] In some embodiments, the amphiphilic block copolymer is selected from the group consisting of a poly(1,2-butadiene)-based copolymer, a poly(1,2-butadiene-co-1,4-butadiene)-based copolymer, a poly(1,2-isoprene)-based copolymer, a poly(1,2-isoprene-co-1,4-isoprene)-based copolymer, a poly(1,4-butadiene)-based copolymer, a poly(1,4-butylene glycol diacrylate)-based copolymer, a poly(1,4-butylene glycol dimethacrylate)-based copolymer, a poly(1,2-isoprene)-based copolymer, a poly(1,2-isoprene)-co-1,4-isoprene)-based copolymer, a poly(1,4-butadiene)-based copolymer, a poly(1,4-butylene glycol diacrylate)-based copolymer, a poly(1,4-butylene glycol dimeth ...The invention also provides copolymers based on poly(2-ethyloxazoline), copolymers based on poly(2-ethylhexyl acrylate), copolymers based on poly(2-hydroxyethyl methacrylate), copolymers based on poly(2-methoxyethyl acrylate), copolymers based on poly(2-methyloxazoline), copolymers based on poly(2-vinylnaphthalene), copolymers based on poly( copolymers based on poly(4-chloromethylstyrene), copolymers based on poly(4-hydroxystyrene), copolymers based on poly(4-styrenesulfonic acid sodium salt), copolymers based on poly(4-styrenesulfonic acid), copolymers based on poly(4-vinylbiphenyl), copolymers based on poly(4-vinylpyridine), copolymers based on poly(4-vinylbenzoic acid), copolymers based on poly(4-vinylpyridine decyl iodide) (poly(4-vinylpyridine) decyliodide)-based copolymer), poly(acrylamide)-based copolymer, poly(acrylate)-based copolymer, poly(acrylic acid sodium salt)-based copolymer, poly(acrylic acid)-based copolymer, poly(acrylonitrile)-based copolymer, poly(adipic anhydride)-based copolymer, poly(alkyl acrylate)-based copolymer, poly(alkyl methacrylate)-based copolymer, poly(alkylsiloxane)-based copolymer, poly(alkylacrylic acid)-based copolymer, poly(alkylene oxide)-based copolymer, poly(butylene oxide)-based copolymer, poly(cyclohexylethylene)-based copolymer, poly(dialkylsiloxane)-based copolymer, poly(diene)-based copolymer, poly(dimethylsiloxane)-based copolymer, poly(ω-silanol-terminated dimethylsiloxane)-based copolymer, poly(ethylene oxide)-based copolymer copolymers based on poly(ethylene oxide), copolymers based on poly(ethylene propylene), copolymers based on poly(ethylene), copolymers based on poly(ethylene-co-butylene), copolymers based on poly(glycerol diacrylate), copolymers based on poly(glycerol dimethacrylate), copolymers based on poly(glycolide), copolymers based on poly(isobutylene), copolymers based on poly(lactide), copolymers based on poly(methacrylate), copolymers based on poly(sodium methacrylate), copolymers based on poly(methacrylic acid), copolymers based on poly(methyl acrylate), copolymers based on poly(methyl methacrylate), copolymers based on poly(methyleneindan), copolymers based on poly(N,N-dimethylacrylamide), copolymers based on poly(methacrylic acid N,copolymers based on poly(4-dimethylaminoethyl ester), copolymers based on poly(n-butyl acrylate), copolymers based on poly(neopentyl 4-styrenesulfonate), copolymers based on poly(neopentyl methacrylate), copolymers based on poly(N-isopropylacrylamide), copolymers based on poly(nitrobenzyl methacrylate), copolymers based on poly(N-methyl 2-vinylpyridinium iodide), copolymers based on poly(N-vinylimidazole), copolymers based on poly(N-vinylpyrrolidone), copolymers based on poly(olefin), copolymers based on poly(propylene oxide diacrylate), copolymers based on poly(propylene oxide dimethacrylate), copolymers based on poly(propylene oxide), copolymers based on poly(p-vinylbenzenesulfonic acid), copolymers based on poly(siloxane), copolymers based on poly(sodium styrenesulfonate), copolymers based on poly(styrene), copolymers based on poly(styrene–copolymers -4-styrenesulfonic acid sodium salt), copolymers based on poly(styrene-co-4-styrenesulfonic acid), copolymers based on poly(sulfonated glycidyl methacrylate), copolymers based on poly(tert-butyl vinyl benzoate), copolymers based on poly(tert-butyl acrylate), copolymers based on poly(tert-butyl methacrylate), copolymers based on poly(tert-butyl methacrylate-co-n-butyl methacrylate), copolymers based on poly(tetrahydrofurfuryl methacrylate), copolymers based on poly(trimethylsiloxy-2-ethyl methacrylate), copolymers based on poly(vinyl alcohol), copolymers based on poly(vinylpyridine), copolymers based on poly(α-methoxy terminated), copolymers based on poly(α-propyl acrylic acid), copolymers based on poly(ε-caprolactone), copolymers based on substituted poly(styrene), copolymers based on poly(methylhydrogensiloxane), and combinations thereof.

[0093] In some embodiments, the amphiphilic block copolymer is end-functionalized, optionally, the amphiphilic block copolymer is acrylate end-capped, alkyl acrylate end-capped, methacrylate end-capped, alkyl methacrylate end-capped, or a combination thereof.

[0094] In some embodiments, the number average molecular weight (M) of each block of the amphiphilic block copolymer is n ) are independently about 1300 to about 32500, about 250 to about 10000, or 2000 to about 8000.

[0095] In some embodiments, the M of the hydrophobic block of the amphiphilic block copolymer is n M with hydrophilic block n The ratio is from about 0.02 to about 128, from about 0.05 to about 20, from about 0.23 to about 10.9, or from about 0.33 to about 3.

[0096] In some embodiments, the amphiphilic block copolymer is poly(ethylene glycol)-b-poly(styrene). In some embodiments, the number average molecular weight (M) of the poly(styrene) block in the poly(ethylene glycol)-b-poly(styrene) is n ) is from about 500 to about 2000. In some embodiments, the M of the poly(ethylene glycol) block of the poly(ethylene glycol)-b-poly(styrene) n From about 2,500 to about 10,000.

[0097] In some embodiments, the ratio of the poly(styrene) block to the poly(ethylene glycol) block in the poly(ethylene glycol)-b-poly(styrene) is n The ratio of is from about 2 to about 5, optionally from about 2.5 to about 4.5 or from about 3 to about 4.

[0098] In some embodiments, the amphiphilic block copolymer is selected from PS(1500)-PEO(6200), PEG5000-PS1600, PS(1300)-PEO(5600) and combinations thereof. It will be understood by those skilled in the art that the term "polyethylene oxide" and the abbreviation "PEO" refer to a polyether compound having the same general chemical structure as polyethylene glycol (PEG).

[0099] In some embodiments, the amphiphilic block copolymer contained in the composite particles is crosslinked. In some embodiments, the amphiphilic block copolymer is crosslinked using a crosslinking method selected from dialdehyde crosslinking, diamine crosslinking, diol crosslinking, ester crosslinking, free radical initiated olefin polymerization, Q-ammonium crosslinking, silane crosslinking, trialdehyde crosslinking, triamine crosslinking, triol crosslinking, urethane crosslinking, and combinations thereof.

[0100] In some embodiments, silane crosslinking is performed with a silane selected from the group consisting of monoalkyl silicates, dialkyl silicates, trialkyl silicates, tetraalkoxy orthosilicates, fumed silica, and combinations thereof. In some embodiments, the tetraalkoxy silicate is selected from the group consisting of tetramethyl orthosilicate (TMOS), tetraethyl orthosilicate (TEOS), and combinations thereof.

[0101] In some embodiments, the free radical initiated olefin polymerization is initiated with a thermally activated and / or photoactivated free radical initiator, the optional free radical initiator being selected from nitrile-based initiators, peroxide-based initiators, and combinations thereof. In some embodiments, the free radical initiator is selected from azobisisobutyronitrile (AIBN), diisopropyl peroxydicarbonate (IPP), benzoyl peroxide (BPO), 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methylpropiophenone, trimethylpropane tris(3-mercaptopropionate), and combinations thereof.

[0102] In some embodiments, the amphiphilic block copolymers included in the composite particles of the present disclosure can be crosslinked using more than one crosslinking method. In some embodiments, the amphiphilic block copolymers are crosslinked using silane crosslinking and free radical initiated olefin polymerization crosslinking. In some embodiments, the amphiphilic block copolymers are crosslinked using TEOS and AIBN.

[0103] In some embodiments, the amphiphilic block copolymer is selected from the group consisting of poly(1,2-butadiene)-b-poly(acrylic acid) crosslinked with AIBN, poly(1,2-butadiene)-b-poly(acrylic acid) crosslinked with fumed silica, poly(1,2-butadiene)-b-poly(acrylic acid) crosslinked with TEOS, poly(1,2-butadiene)-b-poly(acrylic acid) crosslinked with TEOS and AIBN, poly(1,4-butadiene)-b-poly(acrylic acid) crosslinked with AIBN, poly(1,4-butadiene)-b-poly(acrylic acid) crosslinked with TEOS, poly(1,4-butadiene)-b-poly(acrylic acid) crosslinked with TEOS and AIBN, poly(dimethylsiloxane) crosslinked with TEOS, poly(1,2-butadiene)-b-poly(acrylic acid) crosslinked with TEOS, poly(1,4-butadiene)-b-poly(acrylic acid) crosslinked with TEOS, poly(1,4-butadiene)-b-poly(acrylic acid) crosslinked with TEOS, poly(1,4-butadiene)-b-poly(acrylic acid) crosslinked with TEOS, poly(dimethylsiloxane) crosslinked with TEOS, poly(1,2-butadiene)-b-poly(acrylic acid ... AIBN, poly(1,4-butadiene)-b-poly(acrylic acid) crosslinked with TEOS, poly(1,4-butadiene)-b-poly(acrylic )-b-poly(acrylic acid), poly(dimethylsiloxane)-b-poly(ethylene oxide) cross-linked with TEOS, poly(methyl methacrylate)-b-poly(acrylic acid) cross-linked with TEOS, poly(methyl methacrylate)-b-poly(ethylene oxide) cross-linked with TEOS, uncross-linked poly(methyl methacrylate)-b-poly(ethylene oxide), poly(n-butyl acrylate)-b-poly(acrylic acid) cross-linked with TEOS, poly(styrene)-b-poly(ethylene oxide) cross-linked with TEOS, poly(vinyl alcohol)-b-poly(methyl methacrylate) cross-linked with TEOS, poly(vinyl alcohol)-b-poly(styrene) cross-linked with AIBN 15000 -b-Poly(acrylic acid) 6500 , poly(1,2-butadiene) cross-linked with fumed silica 15000 -b-Poly(acrylic acid) 6500 , poly(1,2-butadiene) cross-linked with TEOS 15000 -b-Poly(acrylic acid) 6500 , poly(1,2-butadiene) cross-linked with TEOS and AIBN 15000 -b-Poly(acrylic acid) 6500 , poly(1,4-butadiene) cross-linked with AIBN 9000 -b-Poly(acrylic acid) 3500 , poly(1,4-butadiene) cross-linked with TEOS 9000 -b-Poly(acrylic acid) 3500 , poly(1,4-butadiene) cross-linked with TEOS and AIBN 9000 -b-Poly(acrylic acid) 3500, poly(dimethylsiloxane) cross-linked with TEOS 5000 -b-Poly(ethylene oxide) 2100 , poly(dimethylsiloxane) cross-linked with TEOS 8000 -b-Poly(acrylic acid) 8000 , poly(methyl methacrylate) cross-linked with TEOS 3000 -b-Poly(ethylene oxide) 3000 , uncrosslinked poly(methyl methacrylate) 3000 -b-Poly(ethylene oxide) 3000 , poly(methyl methacrylate) cross-linked with TEOS 7400 -b-Poly(acrylic acid) 24300 , poly(n-butyl acrylate) cross-linked with TEOS 7500 -b-Poly(acrylic acid) 5500 , poly(styrene) cross-linked with TEOS 1300 -b-Poly(ethylene oxide) 5600 , poly(vinyl alcohol) with TEOS 2300 -b-Poly(methyl methacrylate) 25000 , poly(vinyl alcohol) cross-linked with TEOS 2500 -b-Poly(styrene) 12500 , and their combinations.

[0104] In some embodiments, the amphiphilic block copolymer is selected from uncrosslinked poly(methyl methacrylate)-b-poly(ethylene oxide), poly(dimethylsiloxane)-b-poly(acrylic acid) crosslinked with TEOS, poly(methyl methacrylate)-b-poly(acrylic acid) crosslinked with TEOS, poly(1,2-butadiene)-b-poly(acrylic acid) crosslinked with TEOS, poly(1,4-butadiene)-b-poly(acrylic acid) crosslinked with TEOS, poly(dimethylsiloxane)-b-poly(ethylene oxide) crosslinked with TEOS, poly(vinyl alcohol)-b-poly(ethylene oxide) crosslinked with TEOS. ), poly(styrene)-b-poly(ethylene oxide) crosslinked with TEOS, poly(n-butyl acrylate)-b-poly(acrylic acid) crosslinked with TEOS, poly(1,2-butadiene)-b-poly(acrylic acid) crosslinked with AIBN, poly(1,4-butadiene)-b-poly(acrylic acid) crosslinked with AIBN, poly(1,2-butadiene)-b-poly(acrylic acid) crosslinked with TEOS and AIBN, poly(1,4-butadiene)-b-poly(acrylic acid) crosslinked with TEOS and AIBN, and combinations thereof; optionally, the amphiphilic block copolymer is selected from uncrosslinked poly(methyl methacrylate) 3000 -b-Poly(ethylene oxide) 3000 , poly(methyl methacrylate) cross-linked with TEOS 3000 -b-Poly(ethylene oxide)3000 , poly(dimethylsiloxane) cross-linked with TEOS 8000 -b-Poly(acrylic acid) 8000 , poly(methyl methacrylate) cross-linked with TEOS 7400 -b-Poly(acrylic acid) 24300 , poly(1,2-butadiene) cross-linked with TEOS 15000 -b-Poly(acrylic acid) 6500 , poly(1,4-butadiene) cross-linked with TEOS 9000 -b-Poly(acrylic acid) 3500 , poly(dimethylsiloxane) cross-linked with TEOS 5000 -b-Poly(ethylene oxide) 2100 , poly(vinyl alcohol) cross-linked with TEOS 2300 -b-Poly(ethylene oxide) 2100 , poly(styrene) cross-linked with TEOS 1300 -b-Poly(ethylene oxide) 5600 , poly(n-butyl acrylate) cross-linked with TEOS 7500 -b-Poly(acrylic acid) 5500 , poly(1,2-butadiene) cross-linked with AIBN 15000 -b-Poly(acrylic acid) 6500 , poly(1,4-butadiene) cross-linked with AIBN 9000 -b-Poly(acrylic acid) 3500 , poly(1,2-butadiene) cross-linked with TEOS and AIBN 15000 -b-Poly(acrylic acid) 6500 , poly(1,4-butadiene) cross-linked with TEOS and AIBN 9000 -b-Poly(acrylic acid) 3500 , and their combinations.

[0105] When the composite particles are used in contact lenses, the amphiphilic block copolymer can be a biocompatible amphiphilic block copolymer. Such amphiphilic block copolymers are known to those skilled in the art. For example, such amphiphilic block copolymers are suitable for contact with the eyes of a subject.

[0106] In some embodiments, the composite particles have a diameter in the nanometer to micrometer range. In one embodiment, the composite particles have a diameter in the micrometer range. In another embodiment, the composite particles have a diameter in the nanometer range. In some embodiments, the composite particles have a diameter of about 1nm to about 600nm. In some embodiments, the composite particles have a diameter of about 30nm to about 100nm. In some embodiments, the composite particles have a diameter of about 40nm to about 60nm. In some embodiments, the composite particles have a diameter of about 50nm. In some embodiments, the composite particles of the present disclosure have a diameter of about 50 nanometers to about 400 nanometers. In some embodiments, the diameter of the composite particles is about 90 nanometers to about 200 nanometers.

[0107] In some embodiments, the composite particles of the present disclosure comprise more than one hydrophobic dye. In some embodiments, the composite particles of the present disclosure comprise more than one amphiphilic block copolymer.

[0108] In some embodiments, the amphiphilic block copolymer encapsulates the dye in the form of micelles.

[0109] In some embodiments, the composite particles are substantially solvent-free.

[0110] The composite particles of the present disclosure have been shown to be able to withstand specific conditions used in the manufacture of hydrogels, silicone hydrogels, and / or contact lenses.

[0111] In some embodiments, the composite particles are subjected to a 2 The UV-Vis absorption spectrum remained essentially unchanged after 30 minutes of UV exposure.

[0112] In some embodiments, the composite particles are subjected to a 2 The maximum UV-Vis absorbance after 30 minutes of UV exposure was 12.8 mW / cm 2 The absorbance of the present invention is at least 50%, at least 60%, at least 70%, at least 80% or at least 90% of the maximum UV-Vis absorbance before UV exposure.

[0113] In some embodiments, the composite particles have a power of 12.8 mW / cm at 250 nm. 2 The UV-Vis spectrum after photobleaching is substantially unchanged after about 1 minute, about 3 minutes, about 5 minutes, about 10 minutes, or about 15 minutes of UV exposure.

[0114] In some embodiments, the maximum UV-Vis absorbance of the composite particles after photobleaching by UV for about 1 minute, about 3 minutes, about 5 minutes, about 10 minutes, or about 15 minutes is 12.8 mW / cm at 250 nm.2 At least 50%, at least 60%, at least 70%, at least 80% or at least 90% of the maximum UV-Vis absorbance prior to UV exposure.

[0115] In some embodiments, the power is provided by 12.8 mW / cm at 250 nm. 2 After UV exposure for 1 minute, about 3 minutes, about 5 minutes, about 10 minutes or about 15 minutes for photobleaching, the change in the UV-Vis transmission spectrum of the composite particles is less than 80%, less than 70%, less than 60%, less than 50% or less than 40%.

[0116] In some embodiments, the maximum UV-Vis absorbance of the composite particles in water, THF, or a mixture thereof after heating at about 60°C, about 70°C, about 80°C, about 90°C, or about 100°C for about 1 hour, about 3 hours, about 5 hours, about 8 hours, about 10 hours, about 12 hours, about 18 hours, about 24 hours, or about 30 hours is at least 50%, at least 60%, at least 70%, at least 80%, or at least 90% of the maximum UV-Vis absorbance before heating.

[0117] In some embodiments, the UV-Vis absorption spectrum of the composite particles is substantially unchanged after autoclaving in aqueous solution at about 121° C. and 108 kPa.

[0118] In some embodiments, after autoclaving in aqueous solution at about 121° C., 108 kPa, the maximum UV-Vis absorbance of the composite particles is at least 50%, at least 60%, at least 70%, at least 80%, or at least 90% of the maximum UV-Vis absorbance before autoclaving.

[0119] In some embodiments, the UV-Vis absorption spectrum of the composite particles is substantially unchanged after ethanol washing with about 25% v / v, about 50% v / v, about 75% v / v, or about 95% v / v ethanol in water for about 1 hour.

[0120] In some embodiments, the maximum UV-Vis absorbance of the composite particles after ethanol washing for about 1 hour with about 25% v / v, about 50% v / v, about 75% v / v, or about 95% v / v ethanol in water is at least 50%, at least 60%, at least 70%, at least 80%, or at least 90% of the maximum UV-Vis absorbance before the ethanol washing.

[0121] In some embodiments, the composite particles are stable when stored in saline at 50° C. for at least one day, at least three days, at least four days, at least five days, at least 125 hours, at least 130 hours, or at least 136 hours.

[0122] In some embodiments, the UV-Vis absorption spectrum of the composite particles is substantially unchanged after storage in 50°C saline for at least one day, at least three days, at least four days, at least five days, at least 125 hours, at least 130 hours, or at least 136 hours.

[0123] In some embodiments, the maximum UV-Vis absorbance of the composite particles after storage in 50°C saline for at least one day, at least three days, at least four days, at least five days, at least 125 hours, at least 130 hours, or at least 136 hours is at least 50%, at least 60%, at least 70%, at least 80%, or at least 90% of the maximum UV-Vis absorbance before storage.

[0124] In some embodiments, the composite particles have a power of 12.8 mW / cm at 250 nm. 2 The change in maximum UV-Vis absorbance after about 1 minute, about 3 minutes, about 5 minutes, about 10 minutes, or about 15 minutes of UV exposure for photobleaching is less than the change in maximum UV-Vis absorbance of the hydrophobic dye alone at 250 nm after about 1 minute, about 3 minutes, about 5 minutes, about 10 minutes, or about 15 minutes of UV exposure for photobleaching.

[0125] In some embodiments, the composite particles have a power of 12.8 mW / cm at 250 nm. 2 The change in maximum UV-Vis transmittance of the hydrophobic dye after photobleaching at 250 nm for about 1 minute, about 3 minutes, about 5 minutes, about 10 minutes, or about 15 minutes is less than the change in maximum UV-Vis transmittance of the hydrophobic dye alone after photobleaching at 250 nm for about 1 minute, about 3 minutes, about 5 minutes, about 10 minutes, or about 15 minutes, respectively.

[0126] In some embodiments, the change in maximum UV-Vis absorbance of the composite particles after heating at about 60°C, about 70°C, about 80°C, about 90°C, or about 100°C for about 1 hour, about 3 hours, about 5 hours, about 8 hours, about 10 hours, about 12 hours, or about 18 hours is less than the change in maximum UV-Vis absorbance of the hydrophobic dye after heating at about 60°C, about 70°C, about 80°C, about 90°C, or about 100°C for about 1 hour, about 3 hours, about 5 hours, about 8 hours, about 10 hours, about 12 hours, or about 18 hours, respectively.

[0127] In some embodiments, the change in maximum UV-Vis absorbance of the composite particles after autoclaving in aqueous solution at about 121°C, 108 kPa is less than the change in maximum UV-Vis absorbance of the hydrophobic dye after autoclaving in aqueous solution at 121°C, 108 kPa.

[0128] In some embodiments, the change in maximum UV-Vis absorbance of the composite particles after storage in 50°C saline for at least one day, at least three days, at least four days, at least five days, at least 125 hours, at least 130 hours, or at least 136 hours is less than the change in maximum UV-Vis absorbance of the hydrophobic dye after storage in 50°C saline for at least one day, at least three days, at least four days, at least five days, at least 125 hours, at least 130 hours, or at least 136 hours, respectively.

[0129] In some embodiments, the hydrophobic dye has absorbance in a region selected from the ultraviolet region, the visible light region, and combinations thereof. In one embodiment, the hydrophobic dye has absorbance in the ultraviolet region. In another embodiment, the hydrophobic dye has absorbance in the visible light region. In another embodiment, the hydrophobic dye has absorbance in the ultraviolet region and in the visible light region.

[0130] In another aspect, the present disclosure includes a composition comprising one or more composite particles of the present disclosure in a solvent selected from an aqueous solvent, an organic solvent, and mixtures thereof. The present disclosure also includes a composition comprising:

[0131] A composite particle in an aqueous medium, the composite particle comprising:

[0132] hydrophobic dyes; and

[0133] Amphiphilic block copolymers encapsulating hydrophobic dyes,

[0134] The hydrophobic dyes have absorbance in the range from the ultraviolet region to the infrared region of the electromagnetic spectrum.

[0135] Those skilled in the art will appreciate that the composite particles in the compositions of the present disclosure may vary as with respect to the embodiments of the composite particles of the present disclosure.

[0136] In some embodiments, the solvent is an aqueous solvent. In some embodiments, the solvent is water.

[0137] In some embodiments, the organic solvent is water soluble. In some embodiments, the organic solvent is selected from alcohols, ethers, ketones, amides, amines, thiols, aldehydes, carboxylic acids, butanediol, ethanolamine, dimethoxyethane, dimethyl sulfoxide, dioxane, alkylamines, pyrrolidone, propylene glycol, pyridine, and combinations thereof.

[0138] In some embodiments, the organic solvent is selected from ethanol, methanol, propanol, butanol, butoxyethanol, THF, tetrahydropyran (THP), dioxane, DMF, acetone, acetonitrile, N,N-dimethylformamide, dioxane, methyl ethyl ketone, acetaldehyde, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, diethanolamine, diethylenetriamine, dimethoxyethane, ethylamine, methylamine, N-methyl-2-pyrrolidone, 1-propanol, 1,3-propylene glycol, pyridine, and combinations thereof.

[0139] In some embodiments, the compositions of the present disclosure have a thermal conductivity of 12.8 mW / cm 2 The UV-Vis absorption spectrum remained essentially unchanged after 30 minutes of UV exposure.

[0140] In some embodiments, the compositions of the present disclosure are stable in tetrahydrofuran (THF), water, or mixtures thereof for at least: 1 day, 1 week, 3 weeks, 7 weeks, 11 weeks, 3 months, or 6 months. In some embodiments, the compositions of the present disclosure are stable in THF for at least one day, at least one week, at least three weeks, at least seven weeks, or at least 11 weeks. In some embodiments, the compositions of the present disclosure are stable in THF for at least six months.

[0141] In some embodiments, the maximum UV-Vis absorbance of the composition of the present disclosure after heating in water, aqueous THF, or a mixture thereof at about 60° C., about 70° C., about 80° C., about 90° C., or about 100° C. for 15 minutes is at least 50%, at least 60%, at least 70%, at least 80%, or at least 90% of the maximum UV-Vis absorbance before heating. In some embodiments, the UV-Vis absorbance of the composite particle composition of the present disclosure is substantially unchanged when stored at standard room temperature for more than three months.

[0142] In some embodiments, the composition is at 12.8 mW / cm 2 The maximum UV-Vis absorbance after 30 minutes of UV exposure was 12.8 mW / cm 2 The absorbance of the aqueous solution is at least 50%, at least 60%, at least 70%, at least 80% or at least 90% of the maximum UV-Vis absorbance before UV exposure.

[0143] In some embodiments, the composite particles have a power of 12.8 mW / cm at 250 nm. 2 The UV-Vis spectrum after photobleaching is substantially unchanged after about 1 minute, about 3 minutes, about 5 minutes, about 10 minutes, or about 15 minutes of UV exposure.

[0144] In some embodiments, the maximum UV-Vis absorbance of the composition after about 1 minute, about 3 minutes, about 5 minutes, about 10 minutes, or about 15 minutes of photobleaching by UV exposure at 250 nm is 12.8 mW / cm 2 At least 50%, at least 60%, at least 70%, at least 80% or at least 90% of the maximum UV-Vis absorbance prior to UV exposure.

[0145] In some embodiments, the power is provided by 12.8 mW / cm at 250 nm. 2 The UV-Vis transmission spectrum of the composition after about 1 minute, about 3 minutes, about 5 minutes, about 10 minutes, or about 15 minutes of UV exposure for photobleaching changes by less than 80%, less than 70%, less than 60%, less than 50%, or less than 40%.

[0146] In some embodiments, the maximum UV-Vis absorbance of the composition after heating in water, THF, or a mixture thereof at about 60°C, about 70°C, about 80°C, about 90°C, or about 100°C for about 1 hour, about 3 hours, about 5 hours, about 8 hours, about 10 hours, about 12 hours, about 18 hours, about 24 hours, or about 30 hours is at least 50%, at least 60%, at least 70%, at least 80%, or at least 90% of the maximum UV-Vis absorbance before heating.

[0147] In some embodiments, the UV-Vis absorption spectrum of the composition is substantially unchanged after autoclaving in aqueous solution at about 121°C, 108 kPa.

[0148] In some embodiments, the maximum UV-Vis absorbance of the composition after autoclaving in aqueous solution at about 121°C, 108 kPa is at least 50%, at least 60%, at least 70%, at least 80%, or at least 90% of the maximum UV-Vis absorbance before autoclaving.

[0149] In some embodiments, the UV-Vis absorption spectrum of the composition is substantially unchanged after ethanol washing for about 1 hour with about 25% v / v, about 50% v / v, about 75% v / v, or about 95% v / v ethanol in water.

[0150] In some embodiments, the maximum UV-Vis absorbance of the composition after ethanol washing for about 1 hour with about 25% v / v, about 50% v / v, about 75% v / v, or about 95% v / v ethanol in water is at least 50%, at least 60%, at least 70%, at least 80%, or at least 90% of the maximum UV-Vis absorbance before the ethanol wash.

[0151] In some embodiments, the composition is stable when stored in normal saline at 50°C for at least one day, at least three days, at least four days, at least five days, at least 125 hours, at least 130 hours, or at least 136 hours.

[0152] In some embodiments, the UV-Vis absorption spectrum of the composition is substantially unchanged after storage in saline at 50°C for at least one day, at least three days, at least four days, at least five days, at least 125 hours, at least 130 hours, or at least 136 hours.

[0153] In some embodiments, the maximum UV-Vis absorbance of the composition after storage in normal saline at 50° C. for at least one day, at least three days, at least four days, at least five days, at least 125 hours, at least 130 hours, or at least 136 hours is at least 50%, at least 60%, at least 70%, at least 80%, or at least 90% of the maximum UV-Vis absorbance before storage.

[0154] In some embodiments, the composition is stable in aqueous tetrahydrofuran (THF), water, or a mixture thereof for at least one day, at least one week, at least three weeks, at least seven weeks, at least 11 weeks, at least three months, or at least six months.

[0155] In some embodiments, the composition is stable in aqueous THF for at least one day, at least one week, at least three weeks, at least seven weeks, or at least 11 weeks, optionally wherein the composition is stable in THF for at least six months.

[0156] In some embodiments, the compositions of the present disclosure have a FWHM of less than 150 nm. In some embodiments, the FWHM of the composition is less than twice the FWHM of the dye.

[0157] In some embodiments, the composition of the present disclosure is prepared by a method comprising the steps of: preparing a dye / polymer solution comprising a hydrophobic dye and an amphiphilic block copolymer in an organic solvent, and adding the dye / polymer solution to water to obtain a composition in the form of a micellar aqueous solution. In some embodiments, the dye / polymer solution is added to water or the merging of the dye / polymer solution and water is carried out by using a process comprising rapid nano precipitation (or similar encapsulation technology), microfluid mixing, ultrasonic treatment, sonication, mechanical stirring, syringe pump or Pasteur pipette. In another embodiment, the process includes rapid nano precipitation. In some embodiments, water is stirred or mixed during the addition process. In some embodiments, the process further includes a centrifugal micellar aqueous solution to include a supernatant containing the composition.

[0158] In some embodiments, the composition of the present disclosure is prepared by a method comprising the steps of: preparing a dye / polymer solution comprising a hydrophobic dye and an amphiphilic block copolymer in an organic solvent, merging the dye / polymer solution with water, and mixing the dye / polymer solution with water to obtain a composition in the form of a micellar aqueous solution. In some embodiments, merging the dye / polymer solution with water and mixing the dye / polymer solution with water are carried out by using a process comprising rapid nanoprecipitation (or similar encapsulation technology), microfluid mixing, ultrasonication, sonication, mechanical agitation, syringe pump or Pasteur pipette. In another embodiment, the process comprises rapid nanoprecipitation. In some embodiments, the process further comprises a centrifugal micellar aqueous solution to comprise a supernatant containing the composition.

[0159] Therefore, on the other hand, the present disclosure also includes the method for preparing the composition of the present disclosure, which includes preparing the dye / polymer solution comprising hydrophobic dye and amphiphilic block copolymer in an organic solvent, and adding the dye / polymer solution to water to obtain the composition in the form of micellar aqueous solution. In some embodiments, adding the dye / polymer solution to water is carried out by using a process comprising rapid nano precipitation (or similar encapsulation technology), microfluid mixing, ultrasonic treatment, sonication, mechanical agitation, syringe pump or Pasteur pipette. In another embodiment, the process includes rapid nano precipitation. In some embodiments, water is stirred or mixed during addition. In some embodiments, the method further includes centrifugal micellar aqueous solution to obtain the supernatant comprising the composition.

[0160] On the other hand, the present disclosure also includes the method for preparing the composition of the present disclosure, which includes preparing the dye / polymer solution comprising a hydrophobic dye and an amphiphilic block copolymer in an organic solvent, and merging the dye / polymer solution and water, and mixing the dye / polymer solution and water to obtain the composition in the form of micellar aqueous solution. In some embodiments, the merging and mixing of dye / polymer solution and water are carried out by using a process comprising rapid nano precipitation (or similar encapsulation technology), microfluid mixing, ultrasonic treatment, sonication, mechanical agitation, syringe pump or Pasteur pipette. In another embodiment, the process includes rapid nano precipitation. In some embodiments, the method further includes centrifugal micellar aqueous solution to obtain the supernatant comprising the composition.

[0161] Further, the present disclosure includes a method for preparing the composite particles of the present disclosure, which includes preparing a dye / polymer solution comprising a hydrophobic dye and an amphiphilic block copolymer in an organic solvent; adding the dye / polymer solution to water while stirring to obtain composite particles in an aqueous solution; and optionally obtaining the composite particles from the aqueous solution by filtering.

[0162] In another aspect, the present disclosure includes a method for preparing the composite particles of the present disclosure, which includes preparing a dye / polymer solution comprising a hydrophobic dye and an amphiphilic block copolymer in an organic solvent; combining the dye / polymer solution and water, and mixing the dye / polymer solution and water to obtain composite particles in an aqueous solution; and optionally obtaining the composite particles from the aqueous solution by filtering.

[0163] In some embodiments, the composite particles of the present disclosure include amphiphilic block copolymers cross-linked using one or more cross-linking agents. It will be appreciated by those skilled in the art that the cross-linking of the amphiphilic polymers can be carried out using any suitable method known in the art. In one aspect, the present disclosure also includes a method for preparing a composition comprising the composite particles of the present disclosure, comprising preparing a dye / polymer / cross-linking agent solution comprising a hydrophobic dye, an amphiphilic block copolymer, and one or more cross-linking agents in an organic solvent; and adding the dye / polymer / cross-linking agent solution to water while mixing to obtain a micellar aqueous solution.

[0164] In another aspect, the present disclosure also includes a method for preparing a composition comprising the composite particles of the present disclosure, which includes preparing a dye / polymer / crosslinker solution comprising a hydrophobic dye, an amphiphilic block copolymer and one or more crosslinkers in an organic solvent; and combining the dye / polymer / crosslinker solution and water, and mixing the dye / polymer / crosslinker solution and water to obtain an aqueous micellar solution.

[0165] In another aspect, the present disclosure includes a method for preparing the composite particles of the present disclosure, which includes preparing a dye / polymer / cross-linker solution comprising a hydrophobic dye, an amphiphilic block copolymer and a cross-linker in an organic solvent; adding the dye / polymer / cross-linker solution to water while mixing to obtain an aqueous solution; and optionally obtaining the composite particles from the aqueous solution by filtering.

[0166] In another aspect, the present disclosure includes a method for preparing the composite particles of the present disclosure, which includes preparing a dye / polymer / cross-linker solution comprising a hydrophobic dye, an amphiphilic block copolymer and a cross-linker in an organic solvent; combining the dye / polymer / cross-linker solution and water, and mixing the dye / polymer / cross-linker solution and water to obtain an aqueous solution; and optionally obtaining the composite particles from the aqueous solution by filtering.

[0167] In some embodiments, the crosslinking agent is selected from silanes as defined above, heat-activated and / or photo-activated free radical initiators as defined above, and combinations thereof. In some embodiments, the crosslinking agent is selected from silanes as described above and combinations thereof, and the above method includes optionally heating the micellar aqueous solution or aqueous solution. In some embodiments, heating initiates crosslinking. In some embodiments, the crosslinking agent is selected from heat-activated and / or photo-activated free radical initiators, and the above method includes heating and / or UV irradiating the micellar aqueous solution or aqueous solution. In some embodiments, the crosslinking agent is one or more silanes and one or more free radical initiators as defined above, and the above method includes heating and / or UV irradiating the micellar aqueous solution or aqueous solution. In some embodiments, heating and / or UV irradiation initiates a free radical process that causes olefin polymerization crosslinking.

[0168] In some embodiments, the composite particles of the present disclosure further include a cryoprotectant. In some embodiments, the cryoprotectant is PEG 4000. In some embodiments, the method for preparing the composition or composite particles of the present disclosure further includes adding a cryoprotectant to the aqueous solution or the micellar aqueous solution, and drying the aqueous solution or the micellar aqueous solution to obtain dried composite particles. For example, drying can be performed by freeze drying or suction filtration.

[0169] In some embodiments, the organic solvent used in the method for preparing the composition of the present disclosure is selected from THF, dichloromethane, chloroform, N,N-dimethylformamide, dioxane, methanol, ethanol, propanol or other suitable alcohols, ethylene glycol, glycerol, diethyl ether, diisopropyl ether, methyl ethyl ketone, dichlorooxyethane, xylene, acetone, benzene, toluene and combinations thereof. In some embodiments, the organic solvent is THF.

[0170] Since, in some embodiments, the compositions of the present disclosure exhibit stability in organic solvents (e.g., THF) and in aqueous solvents (e.g., water), and at various elevated temperatures, the compositions of the present disclosure may be suitable for use in manufacturing processes involving different conditions (e.g., different solvents and different temperatures). Thus, in some embodiments, the composite particles and / or compositions of the present disclosure may be used as filters in hydrogels (e.g., silicone hydrogels). For example, as filters in contact lenses, optionally wherein the contact lenses are hydrogel-based or silicone hydrogel-based.

[0171] Thus, in another aspect, the present disclosure includes a contact lens comprising one or more composite particles or one or more compositions of the present disclosure.

[0172] In some embodiments, the contact lenses are hydrogel-based or silicone hydrogel-based.

[0173] In some embodiments, the hydrogel or silicone hydrogel is biocompatible and / or suitable for use in an animal subject; optionally, the animal subject is a mammal; optionally, the mammal is a human.

[0174] In some embodiments, the power is provided by 12.8 mW / cm at 250 nm. 2 The maximum UV-Vis absorbance of the contact lens after about 1 minute, about 3 minutes, about 5 minutes, about 10 minutes, or about 15 minutes of UV exposure for photobleaching is 12.8 mW / cm at 250 nm. 2 At least 50%, at least 60%, at least 70%, at least 80% or at least 90% of the maximum UV-Vis absorbance prior to UV exposure.

[0175] In some embodiments, the contact lens is provided by 12.8 mW / cm at 250 nm. 2 The change in the UV-Vis transmission spectrum after about 1 minute, about 3 minutes, about 5 minutes, about 10 minutes, or about 15 minutes of UV exposure for photobleaching is less than 80%, less than 70%, less than 60%, less than 50%, or less than 40%.

[0176] In some embodiments, the UV-Vis absorption spectrum of the contact lens is substantially unchanged after autoclaving in an aqueous solution at about 121° C., 108 kPa.

[0177] In some embodiments, the UV-Vis absorption spectrum of a contact lens is substantially unchanged after ethanol washing for about 1 hour with about 25% v / v, about 50% v / v, about 75% v / v, or about 95% v / v ethanol in water.

[0178] In some embodiments, the maximum UV-Vis absorbance of a contact lens after ethanol washing for about 1 hour with about 25% v / v, about 50% v / v, about 75% v / v, or about 95% v / v ethanol in water is at least 50%, at least 60%, at least 70%, at least 80%, or at least 90% of the maximum UV-Vis absorbance before the ethanol wash.

[0179] In some embodiments, the contact lens is stable when stored in normal saline at 50°C for at least one day, at least three days, at least four days, at least five days, at least 125 hours, at least 130 hours, or at least 136 hours.

[0180] In some embodiments, the UV-Vis absorption spectrum of the contact lens is substantially unchanged after storage in 50°C saline for at least one day, at least three days, at least four days, at least five days, at least 125 hours, at least 130 hours, or at least 136 hours.

[0181] In some embodiments, the maximum UV-Vis absorbance of the contact lens after storage in 50°C saline for at least one day, at least three days, at least four days, at least five days, at least 125 hours, at least 130 hours, or at least 136 hours is at least 50%, at least 60%, at least 70%, at least 80%, or at least 90% of the maximum UV-Vis absorbance before storage.

[0182] In some embodiments, the hydrophobic dye is non-reactive to the hydrogel or silicone hydrogel. For example, the term "non-reactive" as used herein can mean that the dye does not contain functional groups that can participate in the polymerization / cross-linking process that produces the hydrogel. For example, the non-reactive dye is optionally free of vinyl groups or methacrylate groups.

[0183] Any suitable hydrogel polymer material can be used for the contact lenses of the present disclosure. For example, some common hydrogel materials can be prepared from suitable hydrophilic monomers, hydrophobic monomers, siloxane monomers or combinations thereof and optionally suitable crosslinking agents. In some embodiments, those skilled in the art will appreciate that the contact lenses are prepared from materials that are biocompatible or suitable for use in the eyes of a subject. In some embodiments, the subject is an animal subject, such as a human subject.

[0184] For example, the hydrophilic monomers include methyl acrylate, ethyl acrylate, acrylic acid, methyl methacrylate, ethyl methacrylate, 2-hydroxyethyl methacrylate, methacrylic acid, 2,2,2-trifluoroethyl methacrylate, 2,2,3,3,3-pentafluoropropyl methacrylate, hexafluoroisopropyl methacrylate, 1,1,2,2-tetrafluoroethoxy 2-hydroxypropyl methacrylate, ethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, diethylene glycol dimethacrylate, polyethylene glycol dimethacrylate, trimethylolpropane trimethacrylate, pentaerythritol tetramethacrylate, bisphenol A dimethacrylate, ethylene methacrylate, Ester, triallyl trimellitate, and allyl methacrylate, 2-methacryloylcarbamoyloxyethyl methacrylate, 2-2 (2-methacryloyloxycarbamoyloxy)ethyl acrylate, 2-(2-methacryloyloxyethylcarbamoyloxy)propyl methacrylate, 2-methacryloyloxyethylcarbamoyloxytetraethylene glycol methacrylate, methacryloyloxyethyl isocyanate, trifluoroethyl methacrylate, 1,1,2,2-tetraethoxy-2-hydroxypropyl methacrylate, 3-(1,1,2,2-tetrafluoroethoxy)-2-hydroxypropyl methacrylate, hydroxyethyl methacrylate, N-methyl-N-vinylacetamide, Hydroxybutyl methacrylate, glyceryl monomethacrylate, glyceryl dimethacrylate, N-vinyl formamide, N-vinyl-N-ethyl formamide, N-vinyl acetamide, N-vinyl isopropyl amide, N-vinyl-N-methylacetamide, N-vinyl-N-ethylacetamide, N-vinyl pyrrolidone, N-vinyl caprolactam, N-vinyl lactam, 1-vinylazonan-2-one, 2-hydroxypropyl methacrylate, 2-hydroxybutyl acrylate, 4-hydroxybutyl acrylate, glyceryl methacrylate, itaconic acid, fumaric acid, maleic acid, dimethylaminoethyl methacrylate Esters, diethylaminoethyl methacrylate, N,N-dimethylacrylamide, N,N-diethylacrylamide, N-methylacrylamide, methylenebisacrylamide, diacetoneacrylamide, methoxyethylene glycol monomethacrylate, methoxypropylene glycol monoacrylate, fluoroalkyl acrylates, tetrafluoroethyl methacrylate, tetrafluoropropyl methacrylate, pentafluoropropyl methacrylate, trifluoroethyl acrylate, tetrafluoroethyl acrylate, tetrafluoropropyl acrylate, pentafluoropropyl acrylate, hexafluorobutyl acrylate, hexafluoroisopropyl acrylate, polyethylene glycol, ethoxylated alkyl glucoside, methacrylic anhydride, methacryloyl chloride, vinylbenzoyl chloride and N-isopropylacrylamide.

[0185] For example, hydrophobic monomers include isobornyl methacrylate, methyl methacrylate, triallyl isocyanurate, allyl methacrylate, styrene, t-butyl styrene, α-methyl styrene, t-butyl methacrylate, cyclohexyl methacrylate, alkyl methacrylates, fluorinated alkyl methacrylates, long chain acrylamides (e.g., octylacrylamide), cyclopentyl methacrylate, and perfluorocyclohexyl methacrylate.

[0186] For example, a silicone hydrogel may be prepared from any one or more of the above monomers and further include one or more silicone components, such as fluorosilicone acrylates and / or polyorganosiloxanes such as polydimethylsiloxane (PDMS). For example, other siloxane monomers include tris(trimethylsiloxy)silylpropyl methacrylate, bis(trimethylsiloxy)methylsilylpropyl methacrylate, pentamethyldisiloxanepropyl methacrylate, tris(trimethylsiloxy)silylpropoxyethyl methacrylate, tris(polydimethylsiloxy)silylpropyl methacrylate, tris(dimethyltrifluoropropylsiloxy)silylpropyl methacrylate, tetramethyldisiloxanebis(propyl methacrylate), 2-methacryloylcarbamoyloxyethyl methacrylate, 2-2(2-methacryloyloxycarbamoyloxy)ethyl acrylate, 2-(2-methacryloyloxyethylcarbamoyloxy)propyl methacrylate, 2-methacryloyloxyethylcarbamoyloxytetraethylene glycol methacrylate methacryloxyethyl isocyanate, poly(hydroxyethyl methacrylate), polydimethylsiloxane (PDMS), 1,3-bis(3-methacryloyloxypropyl)tetramethyldisiloxane, octamethylcyclotetrasiloxane, 1,3,5-Trimethyltrifluoropropyl-cyclotrisiloxane, 1,3,5,7-tetramethyl-cyclotetrasiloxane, 1,3-bis(3-(2-hydroxyethoxy)propyl)tetramethyldisiloxane, α-butyl-ω-3-(2-hydroxyethoxy)propyl)polydimethylsiloxane, tris(dimethyltrifluoropropylsiloxy)silylpropyl methacrylate, pentamethyldisiloxane methyl methacrylate, tris(trimethylsiloxy)methacryloxypropyl silane, phenyltetramethyl-disiloxane Alkyl ethyl acrylate, methylbis(trimethylsiloxy)methacryloxymethylsilane, 3-tris(trimethylsiloxy)silylpropyl vinylcarbamate, 3-tris(trimethylsiloxy)silylpropyl allylcarbamate, 3-tris(trimethylsiloxy)silylpropyl vinyl carbonate, methacryloxypropyl tris(trimethylsiloxy)silane, 3-methacryloxypropyl bis(trimethylsiloxy)methylsilane and methacryloxypropyl pentamethyldisiloxane.

[0187] The preparation of the hydrogel material may also include the use of suitable cross-linking agents, photopolymerization initiators, thermal initiators, catalysts and / or polymerization inhibitors.

[0188] For example, the crosslinking agent may include ethylene glycol dimethacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, polyethylene glycol dimethacrylate, trimethylolpropane trimethacrylate, pentaerythritol tetramethacrylate, bisphenol A dimethacrylate, vinyl methacrylate, allyl methacrylate, ethylene glycol diacrylate, diethylene glycol diacrylate, triethylene glycol diacrylate, polyethylene glycol diacrylate, trimethylolpropane triacrylate, pentaerythritol tetraacrylate, bisphenol A dimethacrylate, vinyl acrylate, and allyl acrylate.

[0189] For example, the photoinitiator may include benzoin ethyl ether, benzyl dimethyl ketal, α,α-diethoxyacetophenone, and 2,4,6-trimethylbenzoyldiphenylphosphine oxide.

[0190] For example, thermal initiators may include benzoyl peroxide, t-butyl peroxide, azobisisobutyronitrile, and azobisdimethylvaleronitrile.

[0191] For example, the catalyst may include trifluoromethanesulfonic acid, sulfuric acid, and acidic clay.

[0192] For example, the polymerization inhibitor may include hydroquinone, 2,6-di-tert-butyl-4-methylphenol, and p-methoxyphenol.

[0193] Since in some embodiments, the composite particles and / or compositions of the present disclosure can be used to filter or block a range of wavelengths of optical radiation by incorporating different dyes with different absorption characteristics, and / or by using more than one composite particle or composition of the present disclosure, different wavelengths can be selectively blocked. Therefore, in another aspect, the present disclosure includes a method of filtering light, which includes selectively blocking optical radiation using one or more composite particles or compositions of the present disclosure.

[0194] In another aspect, the present disclosure includes the use of one or more composite particles or compositions of the present disclosure as optical filters. In some embodiments, one or more composite particles or compositions of the present disclosure are used as optical filters in contact lenses. In some embodiments, one or more composite particles or compositions of the present disclosure are used as optical filters in hydrogels. In some embodiments, the optical filters selectively block optical radiation.

[0195] In some embodiments, the optical radiation that is selectively blocked is selected from infrared light, UV light, visible light, blue light, and combinations thereof. In some embodiments, the optical radiation that is selectively blocked is UV light or blue light. In one embodiment, the optical radiation that is selectively blocked is infrared light. In another embodiment, the optical radiation that is selectively blocked is UV light. In a further embodiment, the optical radiation that is selectively blocked is visible light, such as red light, blue light, or green light. In another embodiment, the optical radiation that is selectively blocked is blue light. In a further embodiment of the present disclosure, the optical radiation that is selectively blocked is a combination of infrared light, ultraviolet light, visible light, and / or blue light.

[0196] The following non-limiting examples are illustrative of the present disclosure:

[0197] Example

[0198] Example 1 General methods and materials

[0199] Dye Exciton TM ABS 456 and 594 were purchased from Luxottica / Exciton (product numbers 04560, 05940). Block copolymer PS(1500)-PEO(6200) was purchased from Polymer Source, sample #P11112-SEO. Tetrahydrofuran (THF) used was purchased from Fisher Scientific (T397-4).

[0200] Spectrophotometer Quartz Cuvette ( Spectrosil spectrophotometer cells, standard rectangular) were purchased from VWR, catalog #414004-064. The micropipettes used were Fisherbrand TM Finnpipette TM II adjustable volume pipette, 100-1000 μL, Mandel PSR#14440. UV-Vis spectra were acquired on an Agilent Cary TM The UV bleaching experiment was performed using a UV reactor Rayonet Photochemical Reactor (Model RPR-100) with ten 253.7 nm lamps and four 350 nm lamps, with an intensity reading of 12,800 μW / cm 2Dynamic light scattering (DLS) experiments were performed using a DLS instrument, BI-200SM Research Goniometer System (serial number 80615), and a DLS detector, BI-APDx DLS (Brookhaven Instruments, serial number 29244). The DLS instrument and detector were mounted on a TMC vibration controlled clean top (AMETEK Ultra Precision Technologies). The round bottom flask reaction block used was an Optitherm supplied by Chemglass. TM , Radleys Discovery Technologies, RR98072. The condenser used was 21800

[0201] Example 2 Packaging process

[0202] An illustrative example of one embodiment of the dye encapsulation process 10 is shown in Figure 1 In general, Figure 1 The exemplary method shown includes dissolving the dye 12 and the amphiphilic block copolymer 14 in an organic solvent 16 (e.g., THF) to form a mixture, and then adding 18 the mixture to water 20 under conditions suitable for encapsulation to form composite particles 22. Figure 1 As shown in , the amphiphilic block copolymer 14 encapsulates the dye 12 and comprises a hydrophobic core 24 and a hydrophilic shell 26. Three different general procedures for preparing micelles were used:

[0203] General package 1

[0204] In one embodiment, about 50 mg of dye and 50 mg of block copolymer are dissolved in 10 mL of THF. Mild heat may optionally be applied to aid dissolution of the block copolymer. 90 mL of MilliQ TM Water. Use a Pasteur pipette to add the solution of dye and block copolymer to the stirring water over the course of 3.5 minutes at room temperature.

[0205] Universal Encapsulator 2

[0206] About 100mg dyestuff and 100mg block copolymer are dissolved in 20mL THF.Can apply gentle heat optionally to help copolymer dissolution in THF, use syringe to draw the dyestuff / copolymer solution of 10mL gained and be placed on syringe pump.When 1200rpm stirs, the dyestuff / copolymer solution in the syringe is added in 90mL ultrapure water with the speed of 2.115mL / min.

[0207] Optionally, the resulting aqueous micellar solution containing the composite particle composition is centrifuged at 14,000 rpm for 30 minutes, and the supernatant containing the composite particles is retained.

[0208] Universal Encapsulator 3

[0209] About 100mg dye and 100mg block copolymer are dissolved in 20mL THF. Can optionally apply gentle heat to help copolymer dissolution in THF. The dye / copolymer solution of 10mL gained is drawn in the syringe equipped with a needle. Draw 10mL ultrapure water with the different syringes equipped with needles. The syringe equipped with dye / copolymer solution and the syringe equipped with ultrapure water are connected to each arm of closed impact jet (CIJ) mixer. Content is mixed in CIJ to carry out fast nano precipitation (FNP). The mixture is dripped into the 80mL ultrapure water stirred at 1200rpm.

[0210] Optionally, the resulting aqueous micellar solution containing composite particles is centrifuged at 14,000 rpm for 30 minutes, and the supernatant containing the composite particle composition is retained.

[0211] Example 3 Composite particles of Exciton ABS 594, 456 and Epolight 5843

[0212] Epolight 5843

[0213] Dye Epolight TM 5843 was encapsulated with the diblock copolymer PEG5000-PS1600 using General Encapsulation Procedure 1. Figure 2 A comparison of the UV-Vis spectra of the dye before and after encapsulation is shown. The UV-Vis spectrum obtained in THF shows that the unencapsulated dye Epolight 5843 has a maximum absorption peak at 445nm and has a FWHM of 51nm. After encapsulation, a small spectral shift of the dye is observed, and the wavelength observed to produce the maximum absorbance is 451nm, with a FWHM equal to 80nm. Figure 2 The peak broadening and shift shown in is an indication of composite particle formation. Without wishing to be bound by theory, changes in the immediate environment of the dye molecules after encapsulation (e.g., different solvent interactions, different packing of dye molecules within the composite particles) may result in changes in the absorption spectrum. However, the peak shift is small and the peak broadening is minimal, so the composite particle composition will retain the ability to selectively block a specific narrow wavelength range as a filter.

[0214] Fig. 3 shows the physical appearance of dyestuff in water and THF and the encapsulated dyestuff in aqueous environment.Dyestuff is hydrophobic and water-insoluble.In high water content environment, unencapsulated dyestuff is insoluble and is precipitated as pellet in bottle.The encapsulated dyestuff composite particle composition is evenly dispersed in aqueous medium.

[0215] Exciton TM ABS 594 and Exciton TM ABS 456

[0216] The dyes Exciton ABS 594 and Exciton ABS 456 were formulated into composite particles with block copolymer PEG5000-PS1600 according to the general encapsulation procedure 1. Figures 4 and 5 show the comparison between the UV-Vis spectra of the encapsulated and unencapsulated dyes. Figure 4A A comparison of the dye Exciton ABS 594 is shown, while Figure 5A Shown is a spectral comparison of the dye Exciton ABS 456. In comparison with Epolight 5843, similar results were observed.

[0217] Figure 4B and Figure 5B The calibration curves of encapsulated dyes ABS 594 and ABS 456 in 10% THF and 90% water are shown respectively, showing the extinction coefficient of each composite particle composition. A series of dilutions of the composite particles in 10% THF were produced and absorption spectra were collected. The absorbance at the maximum absorption wavelength of each dye was used to generate the calibration curve of each encapsulated dye solution. The dye concentration value was calculated assuming 100% encapsulation efficiency. The obtained extension coefficients prove that the dye Exciton ABS 456 has a lower absorbance than Exciton ABS 594.

[0218] Example 4 Particle size and polydispersity of composite particles

[0219] The composite particle compositions of ABS 594 and ABS 456 prepared with block copolymer PEG5000-PS1600 according to General Encapsulation Procedure 1 were further characterized by tunneling electron microscopy (TEM) and dynamic light scattering (DLS). Fig. 6A and Fig. 7A Representative TEM images of ABS 594 and ABS 456 encapsulated particles are shown in Figure 2, respectively. Figure 6B and Figure 7B Particle size characterization by DLS is provided in.

[0220] TEM results indicated polydisperse particle sizes ranging from 50 nm to 170 nm in diameter. ABS 594 particles qualitatively appeared to be more aggregated than ABS 456. DLS characterization found that the size of the particles ranged from approximately 120 nm to 350 nm.

[0221] Example 5 Notch Filtration

[0222] The mixture of Exciton ABS 594 and Exciton ABS456 composite particles was prepared using block copolymer PEG5000-PS1600 according to the general encapsulation procedure 1, and the UV-Vis absorption spectra were obtained and reported in Figure 8 4 and 5. For example, the ratio of the two dyes can be varied and controlled according to calibration curves such as those provided in FIG. 4 and FIG. 5. The absorption spectra of the mixed encapsulated dyes show that once mixed, the spectral characteristics of each individual encapsulated dye are maintained. The characteristic peaks at 432 nm and 596 nm are attributed to ABS 456 and ABS 594, respectively. The mixing process did not result in further significant peak broadening.

[0223] Example 6 Comparison between general packaging procedures 1 to 3

[0224] 100mg Exciton ABS 456 dye was prepared into composite particles with 100mg block copolymer PS (1500)-PEO (6200) using Universal Encapsulation Procedure 1 to Universal Encapsulation Procedure 3 to compare the efficiency of three programs. For each method, 0.5mL composite particle composition solution was drawn using a volumetric pipette and added to 50mL ultrapure water. The blank used was ultrapure water. UV-Vis absorbance was measured using a UV-Vis spectrometer (Agilent Cary 60 spectrophotometer).

[0225] Fig. 9A Shown are the UV-Vis absorbance of free Exciton ABS 456 dye in THF and encapsulated dye composite particles in aqueous solution prepared with General Encapsulation Procedure 2 using a syringe pump. Fig. 9B Shown is an overlay of UV-Vis absorption spectra of encapsulated dye composite particles centrifuged in aqueous solution prepared with a syringe pump (general encapsulation procedure 2) or a Pasteur pipette (general encapsulation procedure 1). Fig. 9C Shown is an overlay of UV-Vis absorption spectra of centrifuged encapsulated dye composite particles in aqueous solution prepared with a syringe pump (General Encapsulation Procedure 2) or by FNPs (General Encapsulation Procedure 3).

[0226] Since the same micelle concentration was used to measure UV-Vis absorbance, and the absorbance of the micelle prepared using a syringe pump was higher than the absorbance of the micelle prepared using a Pasteur pipette, it may be more effective to encapsulate using a syringe pump in certain embodiments than to encapsulate a Pasteur pipette. Further, the results show that in certain embodiments, using FNP may be more effective than encapsulating dye using a syringe pump. However, all three methods can be used to prepare the composite particle composition of the present application.

[0227] Example 7 Stability of Composite Particle Composition

[0228] Time stability

[0229] Composite particle compositions prepared using General Encapsulation Procedure 3 with dye Exciton ABS 456 and block copolymer PS(1500)-PEO(6200) were stored in aqueous solution at room temperature (rt) in the dark for up to 11 weeks. Aliquots were taken after 1 day, 1 week, 3 weeks, 7 weeks and 11 weeks. UV-Vis absorption spectra were collected to evaluate the stability of the composite particle compositions. Fig.10 An overlay of UV-Vis spectra of aliquots taken at different time points is shown. The results indicate that the light absorption of the composite particle composition remains essentially unchanged over time.

[0230] Stability to UV bleaching

[0231] Exciton ABS 456

[0232] A solution of free dye Exciton ABS 456 in 90% THF and 10% water was placed in a quartz cuvette. 1 mL of a composite particle composition prepared using General Packaging Procedure 3 as described above with dye Exciton ABS 456 and block copolymer PS(1500)-PEO(6200) was diluted in 50 mL of 10% THF / 90% water. The diluted composite particle solution was placed in separate quartz cuvettes. The cuvette containing the free dye solution and the cuvette containing the composite particle solution were heated with 12.8 mW / cm 2 UV-Vis spectra were acquired before UV exposure and after 10, 20 and 30 minutes of UV exposure.

[0233] Fig.11A Comparison between the UV-Vis absorption spectra of the free dye before UV exposure and after UV exposure for different lengths of time is shown. There is a decrease in light absorption at the absorption peak at 458 nm, indicating that the free dye ExcitonABS 456 is bleached under UV.

[0234] Fig. 11BA comparison between the UV-Vis absorption spectra of the composite particles before UV exposure and after different lengths of UV exposure is shown. The absorption spectra are substantially unchanged, indicating that the composite particle composition is stable under UV.

[0235] DLS experiments were performed on the composite particle compositions before and after UV exposure to evaluate particle size and polydispersity characteristics. Figures 12A and 12B show the number distribution and intensity distribution of the composite particle compositions before UV exposure, respectively. Figures 12C and 12D show the number distribution and intensity distribution of the composite particle compositions after UV exposure, respectively. Figures 12E and 12F show scanning electron microscope images of the composite particle compositions before and after UV exposure, respectively, confirming the presence of the composite particles after UV exposure.

[0236] Exciton ABS 594

[0237] Similar UV stability tests described above were repeated for free dye Exciton ABS 594 and composite particles of Exciton ABS 594 and block copolymer PS(1500)-PEO(6200) prepared according to General Encapsulation Procedure 3. Similar results were observed. The free dye solution in 90% THF / 10% water was irradiated at 12.8 mW / cm 2 The quartz crystals were bleached after 30 min of UV exposure, while the composite particles remained essentially unchanged.

[0238] The results of UV stability tests indicate that the structure of the composite particles is more stable to UV exposure than the free dye.

[0239] Example 8 Thermal Stability

[0240] 1 mL of composite particles prepared using General Encapsulation Procedure 3 as described above with dye Exciton ABS 456 and block copolymer PS(1500)-PEO(6200) was diluted in 50 mL of 10% THF / 90% water. The maximum absorbance in the UV-Vis spectrum was determined to be no greater than 1. Ultrapure water was used as a blank for the spectral measurements.

[0241] Obtain the UV-Vis absorbance of the diluted solution before heating. Place approximately 8 mL of the diluted solution in a round bottom flask. Place the round bottom flask in the reaction zone and equip it with a condenser and run cold water through it. After the temperature reaches 100°C, heat the contents of the round bottom flask for 15 minutes. After 15 minutes, stop heating and allow the round bottom flask to cool to room temperature. Obtain the UV-Vis absorbance of the heated solution again.

[0242] Fig.13Shown is a comparison of the UV-Vis absorption spectra of composite particles of dye Exciton ABS 456 before and after heating. Although the maximum UV-Vis absorbance decreases slightly, the absorption peak wavelength is not affected.

[0243] Similar thermal stability tests were performed using the dye Exciton ABS 594 (free dye and composite particles formulated with block copolymer PS(1500)-PEO(6200) using General Encapsulation Procedure 3 as described above) using the procedure described above. The diluted composite particle compositions were heated to 90°C in 10% THF / 90% water for 2 hours. Fig.14 It shows that the absorption spectrum of the composite particles remains basically unchanged before and after heating.

[0244] The thermal stability results indicate that the composite particles are stable enough to be suitable for the manufacturing process for heating to high temperatures in water and THF for different lengths of time.

[0245] Example 9 Stability in organic solvents

[0246] Composite particles were prepared using the dye Exciton ABS 456 and block copolymer PS(1500)-PEO(6200) using General Encapsulation Procedure 3 as described above. 1 mL of the composite particle solution was diluted in 50 mL 90% THF / 10% water. The maximum absorbance in the UV-Vis spectrum was determined to be no greater than 1.

[0247] 1 mL of the diluted composite particle solution was added to a quartz cuvette. 2.5 mL of a 50% THF / 50% water mixture was added to the cuvette. UV-Vis absorption spectra were acquired immediately after addition of the THF / water mixture and after incubation at room temperature for 30 minutes after the addition.

[0248] After incubation at room temperature for 30 min, the cuvette was placed in a photochemical chamber reactor and irradiated with 12.8 mW / cm 2 The UV-Vis absorption spectra were recorded again after UV exposure.

[0249] The above process was repeated using 10% THF / 90% water.

[0250] To test the stability of the composite particles in 99% THF / 1% water, 0.5 mL of undiluted composite particles prepared according to General Encapsulation Procedure 3 were added to 50 mL THF. The peaks were collected at t = 0 min (immediately after addition), t = 30 min (after 30 min incubation at room temperature), and at 12.8 mW / cm 2 UV-Vis absorption spectrum after 10 min of UV exposure.

[0251] Fig.15A Shown are the UV-Vis absorption spectra of composite particles of Exciton ABS 456 in 35% v / v final THF concentration at different time points of the experiment. After 30 minutes of incubation and after UV bleaching, the absorption spectrum remained essentially unchanged.

[0252] Fig. 15B Shown are the UV-Vis absorption spectra of composite particles of Exciton ABS 456 in 10% v / v final THF concentration at different time points of the experiment. After 30 minutes of incubation and after UV bleaching, the absorption spectrum remained essentially unchanged.

[0253] Fig. 15C Shown are the UV-Vis absorption spectra of composite particles of Exciton ABS 456 in 64% v / v final THF concentration at different time points of the experiment. After 30 minutes of incubation and after UV bleaching, the absorption spectrum remained essentially unchanged.

[0254] Fig.15D Shown are the UV-Vis absorption spectra of composite particles of Exciton ABS 456 in 99% v / v final THF concentration at different time points of the experiment. After 30 minutes of incubation and after UV bleaching, the absorption spectrum remained essentially unchanged.

[0255] The results show that the composite particles are stable in different concentrations of the organic solvent THF and are stable to UV bleaching in organic solvents. Fig.11A , the free dye Exciton ABS 456 is not stable to UV bleaching in 90% THF / 10% water.

[0256] Example 10 Contained in a hydrogel

[0257] Si-PDMS macromonomers were prepared and reacted with polyethylene glycol methyl acrylate. A UV activator, diethoxyacetophenone, was added to the mixture. Polymerization was induced by UV light. Encapsulated ABS 456 or ABS594 nanoparticles were added to the mixture just before UV polymerization.

[0258] A polyacrylamide gel was prepared using 1.50 mL of water, 2.15 mL of 40% acrylamide, 1.25 mL of TRIS buffer (pH = 8.6), 50 μL of tetramethylethylenediamine (TEMED), 50 μL of 10% ammonium persulfate, and approximately 200 μL of a stock solution containing encapsulated dyes ABS 456 and ABS 594. The gel was cast between two glass plates at a gel thickness of 1 mm.

[0259] Fig.16An optical image is shown and Fig.17 Shown are the absorption spectra of polyacrylamide gels incorporated with ABS 594 and ABS 456 encapsulated dye micelles. The spectral properties of the encapsulated dyes are maintained after incorporation into the polyacrylamide gel.

[0260] Example 11 Method for preparing composite particles

[0261] Using Zn(II)5,10,15,20-(tetraphenyl)porphyrin and block copolymer poly(1,2-butadiene) 31500 -b-Poly(methyl methacrylate) 21000 Different methods for forming composite particles were tested. Methods included fast nanoprecipitation (FNP), direct injection, ultrasonication, and vortexing. The closed impinging jet (CIJ) mixer used was made by 3D printing and made of high temperature resin. Each method had 5 replicates to test reproducibility. Samples were analyzed using DLS and spectrophotometer to measure reproducibility in terms of particle size, polydispersity, photobleaching rate, and absorbance.

[0262] Methodology Description

[0263] All samples were from the same stock of 2,500 mg / mL block copolymer and dye. 1 ml of the stock was mixed with 9 ml of deionized water using various methods of nanoparticle formation. For the vortex method, 1 ml of the stock was slowly added to the inner wall of a centrifuge tube containing 9 ml of deionized water and then vortexed for 60 seconds. The FNP method had 8 ml of water stirred, and then 1 ml of water and 1 ml of the above stock solution were injected to form nanoparticles. The direct injection method had 9 ml of water stirred in a vial, and then 1 ml of the stock solution was injected through a needle. The ultrasonic generator had 9 ml of water, and then 1 ml of the stock solution was added when the ultrasonic generator was turned on. All samples were centrifuged after formation. All samples were analyzed by spectrophotometer (Agilent 8453) and DLS (Brook-Haven BI-200SM) to measure the reproducibility in terms of particle size, polydispersity, photobleaching rate and absorbance. The samples measured on the spectrophotometer were diluted to 2.5 mg / mL of dye and polymer using deionized water.

[0264] result

[0265] The reproducibility of the formation method was evaluated using UV / Vis spectroscopy. Fig.18 The UV-Vis absorption spectra of the composite particles prepared by each method are shown. The average peak absorbance of the composite particles prepared by each method is shown in Table 1. Each method successfully encapsulated the dye, while the direct injection method and the FNP method showed the highest absorbance.

[0266] Table 1 - Absorbance readings for different particle formation methods

[0267]

[0268] The reproducibility of the formation method was evaluated using particle size analysis. The average particle size for each method is shown in Table 2. All samples showed similar particle size diameters with standard deviations ranging from 11.6 nm to 7.6 nm. The FNP method and ultrasonic treatment showed errors of 14% and 13%. Direct injection and vortexing showed errors of 20% and 22%.

[0269] Table 2 - DLS studies of particles formed using different methods

[0270]

[0271] The study showed that all four methods were able to form nanoparticles.

[0272] Example 12 Packaging Efficiency

[0273] The efficiency of dye encapsulation into composite particles was tested by flocculation. 2 )) Separation of free dye from encapsulated dye. The flocculant can selectively flocculate the dye-containing nanoparticles without flocculating any free dye.

[0274] CaCl 2 Effect of concentration on absorbance

[0275] Using Zn(II)TPP and poly(1,2-butadiene) 31500 -b-Poly(methyl methacrylate) 21000 Three test samples were prepared:

[0276] 1. 2500 mg / mL free dye in tetrahydrofuran (THF);

[0277] 2. 2500 mg / mL of copolymer in tetrahydrofuran (THF); and

[0278] 3. 2500 mg / mL of copolymer and 2500 mg / mL of free dye in tetrahydrofuran (THF).

[0279] Each stock solution was then used to prepare samples using a direct injection method, where 1 ml of sample in THF was injected into 9 mL of aqueous solution stirred in a beaker. The needle tip was submerged and pointed in the direction of stirring. The samples were stirred for 5 minutes.

[0280] This experiment will need to test four aspects, when CaCl 2 The absorbance of the dye in the presence of CaCl2 The absorbance of the dye in the absence of CaCl is determined with negligible differences in the dye content. 2 The concentration of CaCl was confirmed to precipitate all polymer micelles. 2 concentration, and repeating the CaCl 2 concentrations to see the encapsulation efficiency.

[0281] Four tests were performed on the dye samples:

[0282] 1. Mix the dye for 1 hour and then centrifuge

[0283] 2. Stir dye + 25mg / mL CaCl 2 1 hour, then centrifuge

[0284] 3. Stir dye + 50mg / mL CaCl 2 1 hour, then centrifuge

[0285] 4. Stir dye + 100 mg / mL CaCl 2 1 hour, then centrifuge

[0286] Each sample was then measured on a UV-Vis spectrophotometer to determine the dye content. In parallel with these tests, polymer samples were tested to see if all of the polymer had precipitated.

[0287] 1. Stir the polymer for 1 hour and then centrifuge

[0288] 2. Stir polymer + 25 mg / mL CaCl 2 1 hour, then centrifuge

[0289] 3. Stir polymer + 50mg / mL CaCl 2 1 hour, then centrifuge

[0290] 4. Stir polymer + 100 mg / mL CaCl 2 1 hour, then centrifuge

[0291] These samples were evaluated by DLS to determine if particles were still present.

[0292] By measuring different CaCl 2 The absorbance of the solution was used to determine the amount of CaCl 2 The absorbance of the dye in the presence of CaCl 2 The method also determines the absorbance of the dye in the absence of CaCl which has no effect on dye flocculation. 2 It was found that the 2 Compared with samples with 100 mg / mL or lower CaCl2 Under these conditions, the difference in the amount of dye present is negligible.

[0293] Addition of CaCl 2 DLS measurements of the polymers showed that when 100 mg / mL and 50 mg / mL CaCl were added 2 When 25 mg / mL CaCl was added, no nanoparticles were detected. 2 Finally, when no CaCl was added, some small particles could be observed but were difficult to measure. 2 When , nanoparticles were observed with an average particle size of 55 nm and a PDI of 0.117. Since 50 mg / mL did not affect the dye concentration and removed all polymer, 50 mg / mL could be used to determine the encapsulation efficiency.

[0294] Zn(II)TPP and block copolymer poly(1,2-butadiene) 31500 -b-Poly(methyl methacrylate) 21000 The composite particles were compared with particles formed with amphiphilic block copolymer alone and dye alone to evaluate the encapsulation efficiency. Each test object was tested three times.

[0295] Three test samples were prepared using Zn(II)TPP and poly(1,2-butadiene) 31500 -b-Poly(methyl methacrylate) 21000 preparation:

[0296] 1. 250 mg / mL free dye in 1:9 ratio of tetrahydrofuran (THF) / water;

[0297] 2. 250 mg / mL copolymer in 1:9 ratio of tetrahydrofuran (THF) / water; and

[0298] 3. 250 mg / mL copolymer and 250 mg / mL free dye in a 1:9 ratio of tetrahydrofuran (THF) / water.

[0299] Each sample was prepared using a direct injection method where 1 mL of sample in THF was injected into 9 mL of aqueous solution stirred in a beaker. The needle tip was submerged and pointed in the direction of stirring. The sample was stirred for 5 minutes.

[0300] Then add 3 mL of each sample to a separate vial. 2The final concentration that solution makes to be added to each sample is 100mg / mL.Each sample was stirred 1 hour, and at this time, all polymer solutions were precipitated, and no dye solution was precipitated, and the encapsulated dye micellar solution had colored sample precipitation, and some dyes were retained in the solution, so tried three times.Then each sample was centrifuged 1 hour with 80-02 electronic centrifuge with 4000RPM, then decanted.This has removed solid particles, but free dye has been retained in the solution.These samples were measured on UV-Vis spectrophotometer to measure absorbance and use Brookhaven BI-200SM dynamic light scattering device to measure dynamic light scattering (DLS).

[0301] The solution containing only the polymer showed no absorbance for the dye (as expected since no dye was added to the solution at any time). Fig.19 ) The solution containing the dye shows a very large peak for the zinc(II) 5,10,15,20-(tetraphenyl)porphyrin dye, which is heavily diluted and broad. The breadth can be explained by the solution conditions (water) and the dilution factor, since no dye should have been removed. Finally, the solution containing the dye and polymer shows some absorbance (approximately 1 / 10 the absorbance of the dye solution). This would indicate that a significant portion of the dye is removed compared to the free dye. The dye that is removed must be the dye that has been encapsulated, leaving the remaining free dye.

[0302] in conclusion

[0303] After all the encapsulated dye was flocculated out of the solution, the amount of free dye in the solution was determined. The flocculant used was calcium chloride (CaCl 2 ), which can ion-bind to nanoparticle solution and pull them out of solution. Flocculants can selectively flocculate nanoparticles containing dyes without flocculating any free dyes. Calcium chloride at higher concentrations of 33300mg / mL and 1660mg / mL flocculates dye solutions encapsulated in nanoparticles, but also flocculates free dyes. It was found that lower concentrations of 100mg / mL and 50mg / mL flocculate dyes encapsulated in nanoparticles, but do not flocculate free dyes. It was also found by DLS that there were no nanoparticles in solution after adding calcium chloride. After adding 50mg / mL of calcium chloride to the solution of the dye encapsulated in the nanoparticles, and after adding 50mg / mL of calcium chloride to the free dyes, absorbance measurements were performed to measure the amount of unencapsulated dyes in the nanoparticles. The ratio of absorbance measurements showed the percentage of encapsulation, wherein the average corrected absorbance of the free dye solution was 55.8, and the average corrected absorbance of the encapsulated dye solution was 1.33. Comparing these values ​​yields a packing efficiency of 97.6%.

[0304] Using calcium chloride as a flocculant, selective flocculation can occur on dye samples encapsulated in micelles. Tests on poly(1,2-butadiene) 31500 -b-Poly(methyl methacrylate) 21000 The micelles formed using zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) in (diblock copolymer) showed an encapsulation efficiency of 97.6%% + / - 1.57%.

[0305] Example 13 Encapsulation of different dyes

[0306] Eleven structurally diverse hydrophobic dyes were selected to test their ability to be encapsulated by amphiphilic block copolymers.

[0307] 1. 1,3,5,7-Tetramethyl-8-(4-hydroxyphenyl) BODIPY (purchased from PorphyChem) (narrow band, visible light absorber)

[0308] 2.1,7-(di-4,N,N-dimethylaminophenyl)-3,5-(di-4-bromophenyl)AZABODIPY (purchased from PorphyChem) (broadband, visible light absorber)

[0309] 3.2,3,7,8,12,13,17,18-(octabromo)-5,10,15,20-(tetraphenyl)porphyrin (purchased from PorphyChem) (narrow band, visible light absorber)

[0310] 4. Zinc (II) 2,9,16,23-(tetranitro)phthalocyanine (purchased from PorphyChem) (broadband UV absorber)

[0311] 5. 2,3,6,7-Tetrahydro-9-(trifluoromethyl)-1H,5H,11H-[1]benzopyrano(6,7,8-ij)quinolin-11-one (99% dye content), also known as coumarin 153 (purchased from Sigma Aldrich) (broadband, visible light absorber)

[0312] 6. 2,5,7,8-Tetramethyl-2-(4,8,12-trimethyltridecyl)-3,4-dihydro-2H-1-benzopyran-6-yl acetate (>95.5%, liquid), also known as vitamin E or α-tocopherol (purchased from Sigma Aldrich) (broadband, UV absorber)

[0313] 7. 1,3,3-Trimethyl-2-[(1E,3E,5E,7E,9E,11E,13E,15E,17E)-3,7,12,16-tetramethyl-18-(2,6,6-trimethylcyclohexen-1-yl)octadecadien-1,3,5,7,9,11,13,15,17-nonenyl]cyclohexene (>93%, powder), also known as beta-carotene (broadband, visible light absorber)

[0314] 8. Perylene (>99%) (purchased from Sigma Aldrich)

[0315] 9. Vanadyl 2,3-naphthocyanine (purchased from Sigma Aldrich) (narrow band, visible and near infrared absorber)

[0316] 10. p-Quaternary biphenyl (>98%) (purchased from TCI AMERICA) (broadband, UV absorber)

[0317] 11. 2-[3-(2H-benzotriazol-2-yl)-4-hydroxy-phenyl]ethyl methacrylate (99%), also known as NORBLOC TM (Purchased from Sigma Aldrich)

[0318] Polytert-butyl methacrylate (8300)-b-polyethylene oxide (5900) (purchased from Polymer Source) was used for encapsulation.

[0319] A solution of tetrahydrofuran in deionized water (1:9) (10% v / v THF in deionized water) was used as solvent.

[0320] All chemicals and solvents were kept at room temperature, and vitamin E was kept in a dark environment to avoid UV degradation.

[0321] The following 11 composite particles were prepared:

[0322] 1. 1,3,5,7-Tetramethyl-8-(4-hydroxyphenyl) BODIPY in poly(tert-butyl methacrylate) (8300)-b-poly(ethylene oxide) (5900)

[0323] 2. 1,7-(di-4,N,N-dimethylaminophenyl)-3,5-(di-4-bromophenyl)AZABODIPY in poly(tert-butyl methacrylate) (8300)-b-poly(ethylene oxide) (5900)

[0324] 3. 2,3,7,8,12,13,17,18-(octabromo)-5,10,15,20-(tetraphenyl)porphyrin in poly(tert-butyl methacrylate) (8300)-b-poly(ethylene oxide) (5900)

[0325] 4. Zinc(II) 2,9,16,23-(tetranitro)phthalocyanine in poly(tert-butyl methacrylate) (8300)-b-poly(ethylene oxide) (5900)

[0326] 5. Coumarin 153 in poly(tert-butyl methacrylate) (8300)-b-poly(ethylene oxide) (5900)

[0327] 6. Vitamin E in poly(tert-butyl methacrylate) (8300)-b-poly(ethylene oxide) (5900)

[0328] 7. β-Carotene in poly(tert-butyl methacrylate) (8300)-b-poly(ethylene oxide) (5900)

[0329] 8. Perylene in poly(tert-butyl methacrylate) (8300)-b-poly(ethylene oxide) (5900)

[0330] 9. p-Quaterphenyl in poly(tert-butyl methacrylate) (8300)-b-poly(ethylene oxide) (5900)

[0331] 10. Vanadyl 2,3-naphthocyanine in poly(tert-butyl methacrylate) (8300)-b-poly(ethylene oxide) (5900)

[0332] 11. 2-[3-(2H-benzotriazol-2-yl)-4-hydroxy-phenyl]ethyl methacrylate in poly(tert-butyl methacrylate) (8300)-b-poly(ethylene oxide) (5900)

[0333] Encapsulation

[0334] The encapsulation was performed according to the standard rapid nanoprecipitation procedure in a 9:1 deionized water-THF solvent system. 2 ml of 2500 mg / mL poly(tert-butyl methacrylate) (8300)-b-poly(ethylene oxide) (5900) and dye solution were loaded into a 3 mL syringe, and 2 ml of deionized water was prepared in another syringe, which was then used for the encapsulation procedure.

[0335] Characterization

[0336] The main verification method used to verify the success of encapsulation is transmission electron microscopy (TEM). In order to obtain a clear image, the solution after 250mg / mL FNP was diluted 100 times to 2.5mg / mL using the same solvent system and then filtered using a 450nm filter. The filtered sample was dried for 24 hours and imaged using a FEI Tecnai TM Measurements were performed using a 120 kV transmission electron microscope. Images were captured at the most representative regions where particles had sharp edges, a dense core, and a consistent shape.

[0337] Dynamic light scattering (DLS) is used as an indirect method to detect the presence of nanoparticles. In order to obtain accurate measurements, the solution after 250 mg / mL FNP was diluted 100 times to 2.5 mg / mL using filtered deionized water and then filtered using a 450nm filter to remove suspended dust. The filtered samples were measured using a Brook-Haven BI 200-SM ​​dynamic light scattering instrument. Each sample was measured 3 times and the particle size was then interpreted as NNLS, CONTIN or effective diameter.

[0338] The spectra after FNP were measured using an Agilent 8653 spectrophotometer capable of measuring the infrared region. To obtain the most accurate spectral data, the samples were diluted to an absorbance range of 0.5 to 1 using the same solvent system.

[0339] result

[0340] Eleven dyes were successfully encapsulated using the same poly(tert-butyl methacrylate) (8300)-b-poly(ethylene oxide) (5900) diblock copolymer and a 9:1 deionized water-THF solvent system. These dyes include:

[0341] 1.1,3,5,7-Tetramethyl-8-(4-hydroxyphenyl)BODIPY

[0342] 2.1,7-(di-4,N,N-dimethylaminophenyl)-3,5-(di-4-bromophenyl)AZABODIPY

[0343] 3.2,3,7,8,12,13,17,18-(Octabromo)-5,10,15,20-(tetraphenyl)porphyrin

[0344] 4. Zinc (II) 2,9,16,23-(tetranitro)phthalocyanine

[0345] 5. Coumarin 153

[0346] 6. Vitamin E

[0347] 7. Beta-carotene

[0348] 8. Perylene

[0349] 9. p-Quaternary

[0350] 10. Vanadyl 2,3-naphthocyanine

[0351] 11. 2-[3-(2H-benzotriazol-2-yl)-4-hydroxy-phenyl]ethyl methacrylate

[0352] Figure 20 to Figure 21(A to K) show TEM images and UV-Vis absorbance data of particles encapsulating different dyes, indicating that different dyes can be encapsulated into amphiphilic block copolymers while retaining UV-Vis absorbance properties. The particle size and polydispersity results measured by DLS are summarized in Table 3 together with UV-Vis absorbance.

[0353] Table 3 - Particle size and absorbance of particles encapsulating different dyes

[0354]

[0355]

[0356] Example 14 Crosslinking in an amphiphilic block copolymer

[0357] Glutaraldehyde cross-linking

[0358] 20 mL of stock composite particles were prepared using the standard method (described in Example 11 above): the diblock copolymer and the hydrophobic dye were dissolved in 2 mL of THF at a concentration of 2500 mg / mL for both, then injected into a high temperature resin closed impingement jet (CIJ) mixer, another 2 mL of deionized (DI) water was injected, and these solutions were dripped into 16 mL of DI water. PVA (2,500)-PMMA (25,000) loaded with zinc (II) tetraphenylporphyrin was diluted 1000x compared to the stock used for crosslinking experiments, because it was observed that higher concentrations of particles resulted in crosslinking between micelles, as well as visible agglomeration and precipitation of suspended micelles. The concentration of the reagents can be adjusted to avoid agglomeration due to crosslinking between micelles.

[0359] Glutaraldehyde (GA) was added to each of these solutions at different concentrations corresponding to 8.9%, 13.4% and 26.8% molar ratios compared to the PVA end of the diblock copolymer. Once GA was added to each sample, the samples were allowed to react at room temperature for 24 hours before DLS measurement. Four particle samples were prepared at the same dilution, but without the addition of GA as a control for particle size.

[0360] The results of particle size analysis using DLS are shown in Table 4.

[0361] Table 4 - DLS of GA cross-linked particles

[0362]

[0363]

[0364] Polybutadiene cross-linked

[0365] A stock THF solution was prepared at 50 mg / mL of polymer. The sample was then treated with a crosslinker at a concentration of 1% by weight compared to polybutadiene and optionally 1% by weight of TRIS. The test material was prepared using a high temperature resin closed impact jet (CIJ) mixer. After preparation, the particles were inserted into a Falcon tube and centrifuged at 4000 rpm for 30 minutes using a Canfort 80-2 electronic centrifuge. The sample was then heated at 80°C for 24 hours.

[0366] The samples crosslinked with polybutadiene have shown enhanced solvent resistance, indicating that core crosslinking has occurred. CS18 (no crosslinking) did not withstand ethanol exposure, while CS38 (polybutadiene crosslinking) did.

[0367] Tetraethyl orthosilicate (TEOS) crosslinking

[0368] 20 mL of particle solutions containing 100 mg polymer, 100 mg zinc (II) tetraphenylporphyrin (Zn (II) TPP) and 1 mL (0.933 g) TEOS were prepared. These were formed using a direct injection method where the starting materials were dissolved in 2 mL THF and injected into 17 mL water (1 mL TEOS was added so the total volume was 20 mL). The following systems were tested:

[0369] · (1,2)PbD(15,000)-b-PAA(6,500) loaded with Zn(II)TPP and cross-linked with TEOS.

[0370] · (1,2)PbD(31,500)-b-PMMA(21,000) loaded with Zn(II)TPP and cross-linked with TEOS.

[0371] PS(1,300)-b-PEO(5,600) loaded with ZnTPP and cross-linked with TEOS.

[0372] A control sample was prepared in the same manner as the experimental samples above except that no polymer or dye was present. This sample was also prepared using a direct injection method where 1 mL (1.21 g) of TEOS was added to 2 mL of THF and injected into 17 mL of water.

[0373] Each sample was prepared using its own stock solution containing polymer, ZnTPP and TEOS - the stock solution was allowed to mix for 48 hours to ensure the dissolution of the raw materials, and then prepared by direct injection into DI water. Due to the successful solid-state nuclear magnetic resonance (ssNMR) measurement of the required amount of raw materials, these samples were prepared with high concentrations. Once prepared, a small portion of the sample was taken out and diluted 100 times for SEM testing, and then these samples were freeze-dried to remove all water and THF so as to use ssNMR to measure.

[0374] Performing Magic Angle Spin (MAS) 1 H NMR was used to determine the delay time of the slowest proton in the sample at 0.2 ppm corresponding to the hydrogen nucleus adjacent to the silicon nucleus. 29 Si cross-polarization experiments are used to measure the environment of these silicon nuclei. Cross-polarization is a process that places sensitive nuclei ( 1 H) to the less sensitive nucleus ( 29 In addition, this technique allows the observation of the silicon core adjacent to the polymer hydrogen, effectively allowing the incorporation of hydrogen into the silicon shell of the micelle. 29 Measurement of Si cores.

[0375] 29Si and 1H magic angle spinning (MAS) NMR experiments were performed on a Bruker Avance DSX NMR spectrometer with a 9.4 T magnet at NMR-3 at the Department of Chemistry at Dalhousie University (400.24 MHz proton Larmor frequency, 79.52 MHz 29Si Larmor frequency). The samples were loaded into a 4 mm diameter rotor and spun at 7.00 kHz.

[0376] For the 29Si cross polarization (CP) / MAS data of the particles, the 1H parameters need to be known. The 1H MAS NMR spectra were obtained with background suppression after a pulse excitation at a 7kHz sample rotation frequency. The relaxation time for the 1H NMR experiment was determined by an inversion recovery sequence and was estimated to be on the order of 0.84s for the slowest component (at 0.2ppm). The spectrum was obtained with a delay of 4.2s. The chemical shift scale was referenced based on the 29Si chemical shift reference using the conversion factor from IUPAC Recommendations 2001. 29Si (CP) / MAS NMR Experiments NMR experiments were performed at 7.0kH rotation of a 4mm diameter rotor. 29Si CP / MAS NMR spectra were obtained at 4.2s repetition time, 5ms CP contact time, and 1024 scans accumulated. The cross polarization (CP) parameters were optimized on Kaolin, which also served as a secondary chemical shift standard at -91.0ppm and -91.5ppm as a secondary chemical shift reference relative to TMS.

[0377] 29Si CP / MAS NMR spectroscopy Fig. 22 A to C show. Three peaks can be seen, with the shifted positions of the maxima at -91.6ppm, -101.5ppm and -111.0ppm. These agree well with the typical chemical shift values ​​of Q2, Q3 and Q4, respectively. The control sample was prepared exactly the same as the experimental sample in this section, but no polymer or dye was added. After a reaction time of 96 hours and subsequent freeze drying, a white powder was obtained. Measurements of this control sample should then show the signal that the unencapsulated silica in the experimental sample would show. 29Si ssNMR spectrum as shown Fig. 22 D. These NMR results show that TEOS has been successfully hydrolyzed and agglomerated around the composite particles. For the (1,2)PbD(15,000)-b-PAA(6,500) and PS(1,300)-b-PEO(5,600) polymer systems, there are very strong signals compared to the noise, indicating the presence of a large amount of silica in the measured solids. Without wishing to be bound by theory, this can be attributed to the high encapsulation efficiency of these two polymer systems. The low signal-to-noise ratio observed for (1,2)PbD(31,500)-PMMA(21,000) may be due to the low encapsulation efficiency for this system.

[0378] Variation of TEOS concentration. 10 mL of particle solution was prepared containing 2.5 mg polymer, 2.5 mg Zn(II)TPP and different amounts of TEOS as described below. The polymers tested were:

[0379] 1.(1,2)PbD(15,000)-b-PAA(6,500)

[0380] a. Contains 12.5mg TEOS

[0381] b. Contains 5mg TEOS

[0382] c. Contains 2.5mg TEOS

[0383] 2.(1,2)PbD(31,500)-b-PMMA(21,000)

[0384] a. Contains 12.5mg TEOS

[0385] b. Contains 5mg TEOS

[0386] c. Contains 2.5mg TEOS

[0387] 3. PS(1,300)-b-PEO(5,600)

[0388] a. Contains 12.5mg TEOS

[0389] b. Contains 5mg TEOS

[0390] c. Contains 2.5mg TEOS

[0391] 4.PMMA(25,000)-b-PVA(2,300)

[0392] a. Contains 12.5mg TEOS

[0393] b. Contains 5mg TEOS

[0394] c. Contains 2.5mg TEOS

[0395] A stock solution was prepared for each polymer system containing polymer and Zn(II)TPP to ensure the same concentration between different samples – the stock solutions were allowed to mix for 48 hours to ensure dissolution of the starting materials and were subsequently prepared using a high temperature resin closed impingement jet (CIJ) mixer.

[0396] For each sample of the same polymer type, an aliquot was taken and TEOS was added in different amounts, and the volume was corrected using THF to ensure that all samples contained the same concentration of polymer and Zn(II)TPP in the same volume of stock. Once prepared, the samples were diluted 400x for measurement by dynamic light scattering (DLS) and 100x for SEM imaging. The remaining samples were retained for stability studies.

[0397] All samples were kept at room temperature for at least 96 h before any testing to allow TEOS to react and cross-link around the composite particles.

[0398] For all 4 polymer systems tested, DLS was performed to measure particle size and polydispersity. The data are listed in Table 5, Table 6, Table 7 and Table 8 below.

[0399] Table 5 - DLS data for the (1,2)PbD(15000)-b-PAA(6500) polymer system

[0400]

[0401] Table 6 - DLS data for the (1,2)PbD(15000)-b-PMMA(21000) polymer system

[0402]

[0403] Table 7 - DLS data for PS(1300)-b-PEO(5600) polymer system

[0404]

[0405] Table 8 - DLS data for PMMA(25000)-b-PVA(2300) polymer system

[0406]

[0407] DLS data showed particle sizes ranging from 2 nm to over 100 nm.

[0408] TEM imaging ( Fig.23 ) to visualize the particles. Although some agglomeration was observed, this was believed to be due to the slow drying of the water and the stickiness of the polymer upon drying, as the DLS data did not indicate significant agglomeration.

[0409] In this study, synthetic polymer micelles were formed using various polymer systems of (1,2)PbD(15,000)-b-PAA(6,500), (1,2)PbD(31,500)-b-PMMA(21,000), PS(1,300)-b-PEO(5,600) and PMMA(25,000)-b-PVA(2,300). They were successfully cross-linked via TEOS hydrolysis and condensation around the particles. Control samples showed that the unencapsulated polymerized TEOS produced no signal as measured using cross-polarization / magic angle spinning ssNMR. This absence of signal observed in the control samples confirmed that the signal observed in the experimental samples originated from the cross-linked silica shell around the particles and that the CP / MAS ssNMR experiments were insensitive to unencapsulated silica. The signal was clearly observed in the experimental samples studied by NMR. Observation of a signal in 29Si nuclear cross polarization experiments requires close proximity of the silica core to the polymer protons, so observation of a signal in these experiments confirms the presence of polymerized silica around the particles. DLS measurements and SEM imaging confirm the presence of the particles. TEOS cross-linking does not require a reaction between TEOS and the polymer encapsulation, so this cross-linking method can be applied to any polymer system as long as TEOS will be introduced into the core of the particle. This cross-linking method can be performed when the particles are suspended in an aqueous solution to hydrolyze the TEOS prior to condensation. As shown for silica shell cross-linking, TEOS cross-linking can be used in stability studies to determine its effect on stability to solvents, high temperatures and other manufacturing conditions.

[0410] Example 15 Granule Drying

[0411] Poly(1,2-butadiene) 31500 -b-Poly(methyl methacrylate) 21000For encapsulating Zn(II)TPP using the FNP method described above. Polyethylene glycol 4000 (PEG 4000) was used as a cryoprotectant. A stock solution of 250 mg / mL of both block copolymer and dye was prepared in THF. The FNP method had 8 ml of water stirred, followed by 1 ml of water and 1 ml of stock solution to form nanoparticles. All samples were analyzed by spectrophotometer (Agilent) and DLS (Brook-Haven BI-200SM) to measure particle size, polydispersity and absorbance. The samples run on the spectrophotometer were diluted to 5 mg / mL of dye and polymer using deionized water. The samples were at 25 °C during the DLS run and at room temperature during the spectrophotometer run.

[0412] Fig.24 Shown is the UV-Vis spectrum of freeze-dried composite particles with cryoprotectant after resuspension in 90% v / v water / 10% v / v THF. The resuspended particles exhibit a maximum UV absorption at the same wavelength as the non-freeze-dried particles, indicating that the particles are stable to freeze drying.

[0413] Table 9 shows the particle size analysis of the particle samples with cryoprotectant before and after freeze drying. The particle size was essentially unchanged.

[0414] Table 9 - DLS data of particles before and after freeze drying

[0415]

[0416] DLS and TEM data indicate that stock solutions with PEG4000 may have the same size after freeze drying. The stock particle solution containing PEG4000 has an average particle size of 65nm (standard deviation of 11nm), a polydispersity of 0.203 (standard deviation of 0.033). PEG 4000 increases the size of the nanoparticles by 20nm. After the nanoparticles were freeze-dried for 24 hours, they were resuspended in 10% THF / 90% water. The samples were then diluted with water and then measured on DLS. The diameter of the resuspended sample was 62nm (with a standard deviation of 11.3nm) and a polydispersity of 0.205 (with a standard deviation of 0.023), indicating that the particle size of the resuspended sample did not change after freeze drying with a cryoprotectant.

[0417] Example 16 Stability in Hydrogel Monomers and Hydrogel Polymers

[0418] The composite particles of the present disclosure were incorporated into representative contact lens monomers using the M2Dx formulation to simulate the fusion process in contact lens manufacturing. The stability of the particles was evaluated by visual inspection and UV / Vis spectrometry. 14 particles of the present disclosure and 2 comparative examples were incorporated, and all particles were found to withstand exposure to the M2Dx monomer. Unencapsulated zinc (II) 5,10,15,20-(tetraphenyl) porphyrin was also incorporated. All test objects were resuspended uniformly in the M2Dx monomer, and no significant yellowing and turbidity of the solution was observed. Incorporation did not appear to change the filter characteristics in any of the particle composite examples tested. All test objects were then uniformly incorporated into the M2Dx polymer by UV curing, and no significant yellowing and turbidity of the contact lens prototypes was observed. Incorporation did not appear to change the filter characteristics of any of the particle composite examples tested. Therefore, all test objects and controls passed this contact lens prepolymer study.

[0419] In order for the composite particles to be used in contact lenses, they are ideally compatible with the chemical environment of the contact lens matrix and adapted to the homogenization and curing conditions of contact lens manufacturing.

[0420] In this study, candidate particles were evaluated in a representative silicone hydrogel monomer using the M2Dx composition provided by Tangible Science LLC. Nine shell crosslinks, two core crosslinks, two double crosslinks (both shell and core), and two compositions with two crosslinking methods were evaluated in the M2Dx monomer, as well as three comparative examples and two controls. To simulate the manufacturing process, all test materials were dried by vacuum filtration in the presence of the cryoprotectant poly(ethylene glycol) 4000, and then the dried particles were added and homogenized in the M2Dx. The primary evaluation was completed by visual inspection and spectral analysis.

[0421] Test object

[0422] Three comparative particles BC01, PH01 and PN01 were prepared:

[0423] BC01: Dye-encapsulated nanoparticles {zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(2-methyloxazoline) 2400-b-poly(dimethylsiloxane) 5000-b-poly(2-methyloxazoline) 2400 (triblock copolymer)}

[0424] PH01: Dye-encapsulated nanoparticles {Zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(n-butyl acrylate) 7500-b-poly(acrylic acid) 5500 (diblock copolymer)}

[0425] · Nanoparticles encapsulating dye {Zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(ethylene oxide) 4000-b-poly(propylene glycol) 3000-b-poly(ethylene oxide) 4000 (triblock copolymer)}

[0426] Test objects BC01 and PH01 were synthesized in 9:1 deionized water-tetrahydrofuran solvent system according to standard rapid nanoprecipitation (FNP) procedure (as described above). 6mL of 2500mg / L dye-block copolymer and 6mL of deionized water were prepared in two 10ml syringes. Then the stock solution was injected into a 48mL water bath against water while stirring. The solution after FNP was evenly transferred to 3 scintillation vials.

[0427] Fourteen composite particles of the present disclosure were tested:

[0428] 1. CS28 (Coloursmith) dye-encapsulated nanoparticles {zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(dimethylsiloxane) 8000-b-poly(acrylic acid) 8000 (diblock copolymer)}, which were crosslinked in the shell using tetraethyl orthosilicate (5 times the weight of the poly(acrylic acid) block) in the presence of 0.001 M hydrochloric acid at 80 degrees Celsius for 24 hours

[0429] 2. CS29 (Coloursmith) dye-encapsulated nanoparticles {{zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(methyl methacrylate) 7400-b-poly(acrylic acid) 24300 (diblock copolymer)}, which were crosslinked in the shell using tetraethyl orthosilicate (5 times the weight of the poly(acrylic acid) block) in the presence of 0.001 M hydrochloric acid at 80 degrees Celsius for 24 hours

[0430] 3. CS30 (Coloursmith) dye-encapsulated nanoparticles {zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(1,2-butadiene)=-b-poly(acrylic acid) 6500 (diblock copolymer)}, which were crosslinked in the shell using tetraethyl orthosilicate (5 times the weight of the poly(acrylic acid) block) in the presence of 0.001 M hydrochloric acid at 80 degrees Celsius for 24 hours

[0431] 4. CS31 (Coloursmith) dye-encapsulated nanoparticles {zinc (II) 5,10,15,20-(tetraphenyl) porphyrin (dye) poly(dimethylsiloxane) 5000-b-poly(ethylene oxide) 2100 (diblock copolymer)}, which were shell-crosslinked using tetraethyl orthosilicate (5 times the weight of the poly(ethylene oxide) block) and heated at 80 degrees Celsius for 24 hours in the presence of 0.001M hydrochloric acid 5. CS33 (Coloursmith) dye-encapsulated nanoparticles {zinc (II) 5,10,15,20-(tetraphenyl) porphyrin (dye) poly(styrene) 1300-b-poly(ethylene oxide) 5600 (diblock copolymer)}, which were shell-crosslinked using tetraethyl orthosilicate (5 times the weight of the poly(ethylene oxide) block) and heated at 80 degrees Celsius for 24 hours in the presence of 0.001M hydrochloric acid

[0432] 6. CS34 (Coloursmith) dye-encapsulated nanoparticles {zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(n-butyl acrylate) 7500-b-poly(acrylic acid) 5500 (diblock copolymer)}, which were crosslinked in the shell using tetraethyl orthosilicate (5 times the weight of the poly(acrylic acid) block) in the presence of 0.001 M hydrochloric acid at 80 degrees Celsius for 24 hours

[0433] 7. CS35 (Coloursmith) dye-encapsulated nanoparticles {zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(methyl methacrylate) 3000-b-poly(ethylene oxide) 3000 (diblock copolymer)}, which were crosslinked in the shell using tetraethyl orthosilicate (5 times the weight of the poly(ethylene oxide) block) in the presence of 0.001 M hydrochloric acid at 80 degrees Celsius for 24 hours

[0434] 8. CS36 (Coloursmith) dye-encapsulated nanoparticles {zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(1,4-butadiene) 9000-b-poly(acrylic acid) 3500 (diblock copolymer)}, which were crosslinked in the shell using tetraethyl orthosilicate (5 times the weight of the poly(acrylic acid) block) in the presence of 0.001 M hydrochloric acid at 80 degrees Celsius for 24 hours

[0435] 9. CS37 (Coloursmith) dye-encapsulated nanoparticles {zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(1,2-butadiene) 15000-b-poly(acrylic acid) 6500 (diblock copolymer)}, which were crosslinked in the shell using fumed silica (5 times the weight of the poly(acrylic acid) block) heated at 80 degrees Celsius for 24 hours in the presence of 0.001M hydrochloric acid

[0436] 10. CS38 (Coloursmith) dye-encapsulated nanoparticles {zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(1,2-butadiene) 15000-b-polyacrylic acid) 6500 (diblock copolymer)}, which were core-crosslinked by free radicalization in the presence of trimethylolpropane tris(3-mercaptopropionate) using azobisisobutyronitrile (AIBN) initiated at 80 °C for 24 h

[0437] 11. CS39 (Coloursmith) dye-encapsulated nanoparticles {zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(1,4-butadiene) 9000-b-poly(acrylic acid) 3500 (diblock copolymer)}, core crosslinked using azobisisobutyronitrile (AIBN) initiated for 24 hours at 80 degrees Celsius in the presence of trimethylolpropane tris(3-mercaptopropionate)

[0438] 12. CS40 (Coloursmith) dye-encapsulated nanoparticles {zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(1,2-butadiene) 15000-b-poly(acrylic acid) 6500 (diblock copolymer)}, which were crosslinked for shell using tetraethyl orthosilicate (5 times the weight of poly(acrylic acid) block) in the presence of 0.001 M hydrochloric acid and crosslinked for core by free radicalization using azobisisobutyronitrile (AIBN) initiated at 80 degrees Celsius for 24 hours in the presence of trimethylolpropane tris(3-mercaptopropionate)

[0439] 13. CS41 (Coloursmith) Dye-encapsulated nanoparticles {zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(1,4-butadiene) 9000-b-poly(acrylic acid) 3500 (diblock copolymer)}, which were crosslinked for shell using tetraethyl orthosilicate (5 times the weight of poly(acrylic acid) block) in the presence of 0.001 M hydrochloric acid and crosslinked for core by free radicalization using azobisisobutyronitrile (AIBN) initiated at 80 degrees Celsius for 24 hours in the presence of trimethylolpropane tris(3-mercaptopropionate)

[0440] 14. CS42 (Coloursmith) Dye-encapsulated nanoparticles {Zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(methyl methacrylate) 3000-b-poly(ethylene oxide) 3000 (diblock copolymer)}

[0441] The shell cross-linked test articles were synthesized by encapsulating tetraethyl orthosilicate (TEOS) 5 times the weight of the hydrophilic block in the dye block copolymer stock solution. Then, hydrochloric acid (HCl) was added as an acid catalyst at a concentration of 0.001M in a water bath. The particles were made using FNPs and heat treated at 80 degrees Celsius for 24 hours. CS37 used fumed silica instead of TEOS for shell cross-linking. Core cross-linking was achieved by encapsulating the free radical transfer agent trimethylolpropane tris(3-mercaptopropionate (TRIS) and the thermally activated free radical initiator azobisisobutyronitrile (AIBN). The THF used to prepare the stock solution did not contain the free radical inhibitor butylated hydroxytoluene (BHT). The FNPs were then heat treated at 80°C for 24 hours.

[0442] Two controls were included:

[0443] ·CS00 (free dye) Free zinc (II) 5,10,15,20-(tetraphenyl)porphyrin

[0444] Empty M2DX prepolymer

[0445] Double cross-linked test objects (CS40 and CS41) were made by combining two cross-linking methods. AIBN, TRIS and TEOS were encapsulated by FNPs using diblock copolymers with dyes at the same concentrations as described above. The resulting particle solution was heated at 80 degrees Celsius in the presence of HCl.

[0446] To obtain dry nanoparticles, 10 mg / mL poly(ethylene glycol) 4000 was added as a cryoprotectant to each FNP post-solution, and then the particle solution was vacuum dried through a 30 nm membrane filter or air dried.

[0447] Preparation of M2Dx prepolymer and incorporation of particles

[0448] 87.5 mL of M2Dx stock solution was prepared by mixing 14 mL of methacryloyloxypropyl terminated polydimethylsiloxane (M2Dx), 28 mL of methacrylate 3-[tris(trimethylsiloxy)silyl]propyl ester (Tris), 28 mL of dimethylacrylamide (DMA) and 17.5 mL of 1-hexanol. The solution was stirred and stored in an amber glass bottle to prevent undesirable polymerization. The stock was stirred for 24 hours before particle incorporation.

[0449] Since the dried particles could not be separated from the filter, it was impossible to quantitatively transfer the particles from the filter to each prepolymer solution. Therefore, a 2.0 mm x 0.5 mm strip was cut from the filter using a scalpel and fully immersed in 0.5 mL of the M2Dx prepolymer solution to obtain a concentrated particle-containing M2Dx solution.

[0450] The standard spectrum was obtained by measuring a M2Dx prepolymer solution containing 1 mg / mL freeze-dried particles (containing PEG 4000), which has been shown to have approximately 50% light transmittance at 426 nm after polymerization into a gel. The standard absorbance value of the secondary peak at 560 nm was determined to be approximately 0.5. The test material was then prepared by gradually adding a small amount of concentrated M2Dx solution containing particles of unknown concentration to 1.5 mL of M2Dx stock and measuring on an Agilent 8453 spectrophotometer until its spectrum and secondary absorbance matched the standard.

[0451] Evaluation of M2Dx prepolymer

[0452] Evaluation of the M2Dx solution containing the particles by spectroscopic measurements and visual inspection. The spectra of the test objects were checked during the incorporation phase of the particles and the M2Dx solution was visually inspected.

[0453] result

[0454] All test substances, including free dye, could be uniformly resuspended in the M2Dx prepolymer. Visual inspection of the prepolymer containing particles revealed no obvious abnormalities. Fig.25 As shown in , the spectra of all the test substances have the same characteristic peaks as zinc (II) 5,10,15,20-(tetraphenyl)porphyrin.

[0455] Polymerization of M2Dx matrix

[0456] The contact lens prototype was polymerized in a mold assembled by sandwiching an aluminum frame with a specified volume of 1 mL between two glass slides. Before the mold was assembled, an oil-based release agent was sprayed onto the frame and the glass slides as a release agent. The mold was placed in a plastic bag and pressure was applied to the glass slides using 4 clamps to avoid leakage. Once the spectral measurement was performed, 10 μl of the photoinitiator 2-hydroxy-2-methylpropiophenone (Darocure TM 1173) is added to the M2Dx solution containing particles. Then a 3mL syringe is used to inject the solution into the mold through the inlet. Once the solution is loaded, the bag is vacuum sealed using a vacuum sealer and then placed in a UV chamber. The M2Dx solution is UV cured in a plastic bag for 10 minutes. Once the curing process is completed, the gel is carefully transferred from the mold to a scintillation vial containing 20mL deionized water using round-tipped tweezers.

[0457] Evaluation of M2Dx polymers

[0458] The M2Dx polymers containing particles were evaluated by spectral measurements and visual inspection. To obtain good spectral data, the spectrophotometer was blanked using an empty M2Dx gel prepared using the same procedure, and the gel was wiped with a Kimwipe to remove water before spectral measurements. All prototypes were visually inspected to ensure high-quality test pieces with no visual anomalies. To correct the baseline of the samples, an average value from 700nm to 1000nm was taken for each sample and then subtracted from the absorbance at each wavelength. All test pieces, including free dyes, can be UV cured into M2Dx polymers. Fig.26 A representative picture of the M2Dx polymer gel from all samples tested is shown, and no obvious abnormalities were observed. However, all tested samples had varying degrees of coloration. UV-Vis absorption spectra of each M2Dx polymer containing different composite particles were obtained and analyzed in Fig. 27 A shows the transmission spectrum at Fig. 27 Shown in B.

[0459] Since the M2Dx polymer itself has no optical properties and visual features, the absorption peaks of the test objects can be attributed to the incorporation of different particles. The incorporation of the particles of the present disclosure can impart an absorbance corresponding to the absorbance of the dye encapsulated in the composite particles.

[0460] Example 17 Filtering in contact lenses

[0461] This study demonstrates the optical properties of various composite particles of the present disclosure incorporated into representative silicone hydrogel lenses. The purpose is to compare the ability of the test samples to limit light exposure in, for example, the blue light harmful region of the spectrum (400-450nm). The test samples were prepared by dosing the dried particle complex into the M2Dx formulation monomer and then polymerizing to prepare the lens. The spectra of contact lenses containing the test samples showed that they were harmful blue light blockers, and all test samples showed the same characteristic peaks as the control containing free zinc (II) 5,10,15,20-(tetraphenyl) porphyrin (Zn (II) TPP) dye, indicating that encapsulation did not change the shape of the spectrum of the dye payload. In addition, with the exception of CS28, encapsulation had no effect on the sample bandwidth. Encapsulation using poly (dimethylsiloxane) 8000-b-poly (acrylic acid) 8000 (diblock copolymer) broadened the spectrum of the dye payload of the polymer system by 8nm.

[0462] Comparatives BC01, PH01 and PN01 were used. Composite particles CS28 to CS42 of the present disclosure were prepared and tested as described above. M2Dx prepolymers were prepared as described above. Two controls CS00 (free dye) and empty M2Dx polymers were also prepared as described above and used in this study. The particles were dried with the cryoprotectant PEG4000. Except for PN01, which was filtered with a 10nm membrane filter, the particle solution was vacuum dried through a 30nm membrane filter. Test objects CS42 and PN01 could not be filtered with 30nm or 10nm membrane filters, indicating that the particles were less than 10nm or had low encapsulation efficiency. As a result, CS42 and PN01 were air-dried at room temperature. M2Dx prepolymers were mixed with each particle and polymerized as described above.

[0463] The gels were measured using UV / Vis spectrometry to evaluate their optical properties. The spectrophotometer was blanked using M2Dx gels without particles. To correct the baseline of the samples, an average value from 700 to 1000 nm was taken for each sample and then subtracted from the absorbance value at each wavelength.

[0464] The optical properties of the M2Dx polymer gels are summarized in Table 10.

[0465] Table 10 - Optical properties of M2Dx polymers with different particles

[0466]

[0467] All test and control materials had shapes, bandwidths, and peak wavelengths consistent with the free dye in THF. A slight broadening of the bandwidth of CS28 was observed (19 nm). The characteristic peaks of all test and control materials were detected in the blue light harmful region (410 to 450 nm) with a peak position at 425 nm. Due to the change in solvent system, a peak shift of 3 nm was observed for all test and control materials compared to the free dye in THF. By comparing the control materials with the test materials, it can be confidently concluded that encapsulation does not significantly change the absorption spectrum of zinc (II) 5,10,15,20-(tetraphenyl) porphyrin dye.

[0468] Example 18 Ethanol Extraction of Contact Lenses Containing Composite Particles

[0469] In contact lens manufacturing, the prepared contact lenses are subjected to a series of ethanol washing steps to remove any unreacted monomers so that the lenses are safe for entry into the eye. Ideally, the dye incorporated into the contact lens via the composite particles should not be extracted from the contact lens by ethanol washing.

[0470] Comparatives BC01, PH01 and PN01 were used. Composite particles CS28 to CS42 of the present disclosure were prepared and tested as described above. M2Dx prepolymer was prepared as described above. Two controls CS00 (free dye) and empty M2Dx polymer were also prepared as described above and used in this study.

[0471] After gel preparation and cutting into the size required for this experiment, all gels were kept in vials of deionized (DI) water for 24 hours to allow them to hydrate.

[0472] The samples were removed from their water vials and placed in empty and labeled scintillation vials. At time = 0, all samples were simultaneously poured into 10 mL of 25% ethanol extraction solution and the gels were kept soaking in this solution for 1 hour. At the 1 hour mark, the gels were removed from the solution and placed in water vials to quickly stop the extraction. At this point, both the gels and ethanol were measured using a UV / Vis spectrometer with appropriate blanks.

[0473] The process was repeated for the 50%, 75%, and 95% ethanol extraction steps, using a volume of 10 mL for each extraction solution. The solution was not stirred to avoid damaging the gel, which would have become more susceptible to cracking after exposure to ethanol. Note that no measurements were taken on the gel after the 75% ethanol extraction, as the gel appeared to have become more fragile and gel cracking was a concern.

[0474] UV-Vis absorbance measurements were performed on all gels. A correction factor was applied to account for the different amounts of particles in each gel sample.

[0475] Table 11 - Correction Factors

[0476] Test object Initial absorbance in gel Correction factor BC01 0.70038 0.89789 PH01 0.60436 0.77479 PN01 0.09900 0.12691 CS00 0.69044 0.88515 CS28* 0.19533 0.25041 CS29 0.71821 0.92074 CS30 0.28881 0.37026 CS31 0.55946 0.71722 CS32 0.18546 0.23776 CS33 0.43053 0.55194 CS34 0.69911 0.89626 CS35 0.64609 0.82829 CS36 0.78003 1.00000 CS37 0.42686 0.54723 CS38 0.58602 0.75127 CS39 0.69006 0.88465 CS40 0.32513 0.41682 CS41 0.61530 0.78881 CS42 1.12866 1.44694

[0477] The absorbance readings in ethanol are listed in Table 12 below. Because the 25% and 50% ethanol extracts did not result in any absorbance readings, these results are not included. The absorbance values ​​shown are corrected using a correction factor, where the actual absorbance is divided by the correction factor to account for differences in initial absorbance in the gel. The absorbance measured in the 75% and 95% washes are added together to give the absorbance loss in the ethanol wash. The lower total absorbance in EtOH indicates that the extraction of the dye is lower by the ethanol wash.

[0478] Table 12 - Absorbance measured in 75% and 95% ethanol extractions

[0479] Test object Absorbance in 75% Et0H Absorbance in 95% Et0H Total absorbance in Et0H BC01 0.028 0.074 0.103 PH01 0.023 0.034 0.058 PN01* 0.087 0.220 0.307 CS00 0.013 0.026 0.039 CS28* 0.000 0.014 0.014 CS29 0.021 0.052 0.072 CS30 0.015 0.076 0.090 CS31 0.007 0.048 0.056 CS32* 0.068 0.372 0.439 CS33 0.000 0.070 0.070 CS34 0.006 0.019 0.024 CS35 0.016 0.060 0.076 CS36 0.015 0.075 0.090 CS37 0.008 0.044 0.052 CS38 0.016 0.045 0.061 CS39 0.020 0.073 0.093 CS40 0.008 0.051 0.059 CS41 0.012 0.040 0.052 CS42 0.006 0.003 0.009

[0480] Representative UV-Vis absorption spectra of CS42 gel, CS34 gel, CS37 gel and CS41 gel and their corresponding 95% ethanol washes are shown in Fig.28 (A to D) are shown.

[0481] Based on UV-Vis absorption spectra, the composite particles of the present disclosure are able to resist ethanol leaching. In particular, CS28, CS34 and CS42 outperform the control free dye CS00.

[0482] Example 19 Thermal stability of particles in contact lenses

[0483] An autoclave procedure is used in contact lens manufacturing to sterilize contact lenses after packaging. Contact lens manufacturers use autoclaves to sterilize contact lenses immersed in saline. Autoclave conditions involve holding the samples at 121°C and 108 kPa for 30 minutes. The composite particles have been incorporated into a representative contact lens gel and then exposed to autoclave conditions for 30 minutes. After the autoclave process, the saline storage solution and gel were measured on a spectrophotometer. It was found that all samples tested in this study had no leaching into the saline. Neither the absorption spectrum nor the filtering ability of the additives changed through the autoclave process.

[0484] M2Dx gels containing different composite particles were prepared as described above. Comparatives BC01 and PH01 were used. Composite particles CS28 to CS31 and CS33 to CS41 of the present disclosure were prepared and tested as described above. M2Dx prepolymers were prepared as described above. Two controls CS00 (free dye) and empty M2Dx polymers were also prepared as described above and used in this study.

[0485] All test articles were cut into 2cmx2cm gels and then added to scintillation vials containing 5mL of saline. The samples were then subjected to a preset "L30 cycle" autoclave sterilization process, meaning that the samples were subjected to sterile conditions for 30 minutes. The brand and model of the autoclave was AMSCO Steris.

[0486] Representative UV-Vis absorption spectra are Fig.29 The UV-Vis absorbance of the saline solution after autoclaving was also measured. Fig.30 As shown in , no absorption peak corresponding to the encapsulated dye was observed.

[0487] This study shows that the autoclave process does not cause the composite particles of the present disclosure to leach into saline. The results also show that autoclave does not affect the light filtering ability of the additive. From the absorbance of the gel, there is no significant change before or after the autoclave process.

[0488] Example 20 Solvent Stability of Contact Lenses

[0489] The manufacture of contact lenses often involves the use of organic solvents. Primary solvents may include ethanol, hexanol, butoxyethanol, nonanol, and tert-amyl alcohol. The particles tested and their corresponding codes are listed below.

[0490] 1. CS09-Dye-encapsulated nanoparticles {Zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(1,2-butadiene) 31,000-b-poly(methyl methacrylate) 21,500 (diblock copolymer)}

[0491] 2. CS01 - Dye encapsulated dye nanoparticles crosslinked by tetraethyl orthosilicate (5 times the weight of the hydrophilic block) {Zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(1,2-butadiene) 31,000-b-poly(methyl methacrylate) 21,500 (diblock copolymer)}

[0492] 3. CS13 – Dye encapsulated nanoparticles {zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(1,2-butadiene) 31,000-b-poly(methyl methacrylate) 21,500 (diblock copolymer)} cross-linked by tetraethyl orthosilicate (5 times the weight of the hydrophilic block) and hydrochloric acid

[0493] 4. PN01-Dye-encapsulated nanoparticles {Zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(ethylene oxide) 4000-b-poly(methylethylene oxide) 3000-b-poly(ethylene oxide) 4000 (triblock copolymer)}

[0494] 5. CS14 - Nanoparticles encapsulating dye {Zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(ethylene oxide) 4000-b-poly(methylethylene oxide) 3000-b-poly(ethylene oxide) (triblock copolymer) 4000} crosslinked by tetraethyl orthosilicate (5 times the weight of the hydrophilic block) and by free radicalization (1%)

[0495] 6. CS15 – Dye encapsulated nanoparticles {Zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(ethylene oxide) 4000-b-poly(methyl ethylene oxide) 3000-b-poly(ethylene oxide) 4000 (triblock copolymer)} cross-linked by tetraethyl orthosilicate (5 times the weight of the hydrophilic block) and hydrochloric acid

[0496] 7. CS16-Dye-encapsulated nanoparticles {Zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(dimethylsiloxane) 8000-b-poly(acrylic acid) 8000 (diblock copolymer)}

[0497] 8. CS17 – Dye encapsulated nanoparticles {Zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(dimethylsiloxane) 8000-b-poly(acrylic acid) 8000 (diblock copolymer)} crosslinked with tetraethyl orthosilicate (5 times the weight of the hydrophilic block)

[0498] 9. CS18-Dye-encapsulated nanoparticles {Zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(1,2-butadiene) 15000-b-poly(acrylic acid) 6500 (diblock copolymer)}

[0499] 10. CS19 – Dye-encapsulated nanoparticles {zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(1,2-butadiene) 15000-b-poly(acrylic acid) 6500 (diblock copolymer)} by tetraethyl orthosilicate, free radicalization and acid crosslinking

[0500] 11. CS20 – Encapsulated dye nanoparticles {zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(1,2-butadiene) 15000-b-poly(acrylic acid) 6500 (diblock copolymer)} by tetraethyl orthosilicate, free radicalization, acid and thermal crosslinking

[0501] 12.CS21 - Dye-encapsulated nanoparticles {zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(1,2-butadiene) 15000-b-poly(acrylic acid) 6500 (diblock copolymer)} crosslinked by tetraethyl orthosilicate and free radicalization

[0502] 13. CS22 – Dye-encapsulated nanoparticles {zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(1,2-butadiene) 15000-b-poly(acrylic acid) 6500 (diblock copolymer)} by tetraethyl orthosilicate, free radicalization and thermal crosslinking

[0503] 14.CS04 – Dye encapsulated nanoparticles {zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(1,2-butadiene) 15000-b-poly(acrylic acid) 6500 (diblock copolymer)} crosslinked by tetraethyl orthosilicate (5 times the weight of the hydrophilic block)

[0504] 15. CS23 – Dye encapsulated nanoparticles {zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(1,2-butadiene) 15000-b-poly(acrylic acid) 6500 (diblock copolymer)} crosslinked by tetraethyl orthosilicate (20 times the weight of the hydrophilic block)

[0505] 16. CS27 - Dye encapsulated nanoparticles {Zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(vinyl alcohol) 2300-b-poly(methyl methacrylate) 25000 (diblock copolymer)}) with shell crosslinking using tetraethyl orthosilicate (5 times the weight of poly(acrylic acid) block) heated at 80 °C for 24 h in the presence of 0.001 M hydrochloric acid

[0506] 17.CS28 - Dye encapsulated nanoparticles {Zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(dimethylsiloxane) 8000-b-poly(acrylic acid) 8000 (diblock copolymer)} with shell crosslinking using tetraethyl orthosilicate (5 times the weight of poly(acrylic acid) block) heated at 80°C for 24 hours in the presence of 0.001 M hydrochloric acid

[0507] 18.CS29 - Dye encapsulated nanoparticles {Zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(methyl methacrylate) 7400-b-poly(acrylic acid) 24300 (diblock copolymer)} with shell crosslinking using tetraethyl orthosilicate (5 times the weight of poly(acrylic acid) block) heated at 80 °C for 24 h in the presence of 0.001 M hydrochloric acid

[0508] 19. CS30 - Dye encapsulated nanoparticles {Zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(1,2-butadiene)=-b-poly(acrylic acid) 6500 (diblock copolymer)} with shell crosslinking using tetraethyl orthosilicate (5 times the weight of poly(acrylic acid) block) heated at 80°C for 24 hours in the presence of 0.001 M hydrochloric acid

[0509] 20.CS31 - Dye-encapsulated nanoparticles {Zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(dimethylsiloxane) 5000-b-poly(ethylene oxide) 2100 (diblock copolymer)} with shell crosslinking using tetraethyl orthosilicate (5 times the weight of poly(ethylene oxide) block) heated at 80 °C for 24 h in the presence of 0.001 M hydrochloric acid

[0510] 21.CS33 – Dye-encapsulated nanoparticles {Zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(styrene) 1300-b-poly(ethylene oxide) 5600 (diblock copolymer)} with shell crosslinking using tetraethyl orthosilicate (5 times the weight of poly(ethylene oxide) block) heated at 80°C for 24 hours in the presence of 0.001 M hydrochloric acid

[0511] 22.CS34 – Dye-encapsulated nanoparticles {Zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(n-butyl acrylate) 7500-b-poly(acrylic acid) 5500 (diblock copolymer)} with shell crosslinking using tetraethyl orthosilicate (5 times the weight of poly(acrylic acid) block) heated at 80°C for 24 hours in the presence of 0.001 M hydrochloric acid

[0512] 23.CS35 - Dye-encapsulated nanoparticles {Zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(methyl methacrylate) 3000-b-poly(ethylene oxide) 3000 (diblock copolymer)} with shell crosslinking using tetraethyl orthosilicate (5 times the weight of poly(ethylene oxide) block) heated at 80°C for 24 hours in the presence of 0.001 M hydrochloric acid

[0513] 24. CS36 – Dye-encapsulated nanoparticles {Zinc(II) 5,10,15,20-(tetraphenyl)porphyrin (dye) poly(1,4-butadiene) 9000-b-poly(acrylic acid) 3500 (diblock copolymer)} with shell crosslinking using tetraethyl orthosilicate (5 times the weight of poly(acrylic acid) block) heated at 80°C for 24 hours in the presence of 0.001 M hydrochloric acid

[0514] The composite particles are prepared and dried as described above where appropriate.

[0515] This study was conducted over three experimental sessions to determine the effects of solvent washing on the preparation of synthetic polymer micelles. Samples were prepared in tetrahydrofuran (THF) at a concentration of 2,500 mg / mL for both block copolymer and dye. Using FNP, 2 ml of stock was mixed with 18 ml of deionized water to obtain a final concentration of 250 mg / mL. FNP had 16 ml of stirred water, and then 2 ml of water and 2 ml of stock solution were added by syringe using a metal closed impact jet (CIJ) mixer device to form synthetic polymer micelles. All samples were centrifuged at 4000 RPM for 1 hour using an 80-2 electronic centrifuge after formation. These samples were then exposed to a 50% ethanol solution to understand the situation of ethanol exposure (0.5 mL sample with 0.5 mL ethanol) and then the resulting samples were vortexed for 15 seconds and left overnight. The solutions were then compared using a spectrophotometer and visual inspection. All dynamic light scattering (DLS) samples were prepared by diluting the composite particle sample (100 times) and filtering it through a 450 nm filter using a Brookhaven TM The particle size measurements were analyzed using a BI-200SM instrument. Preparation for visual characterization requires that the samples be photographed individually in a photobox with stock and ethanol-treated samples. The first experiment was to determine which composite particles can withstand exposure to 50% ethanol overnight. The samples that can best withstand ethanol exposure will be tested on more solvents. In addition, the stock solution (diluted 100 times) was measured to compare the absorbance loss in the samples.

[0516] The second experiment used the test materials that were most tolerant to ethanol washing in the first experiment and were evaluated by absorbance and visual inspection. These test materials were then further tested in this experiment to determine the effects of various solvents used in the manufacture of contact lenses on different composite particle formulations. The following test materials were used in this experiment: CS17, CS20, CS22, and CS04. In order to test the effects of solvents on composite particle solutions, 0.5 mL of each sample was first placed in a centrifuge tube for each solvent to be tested. Each sample was added with 0.5 mL of hexanol, butoxyethanol, methanol, tert-amyl alcohol, or nonanol to obtain a 50% alcohol solution. All the resulting samples were then vortexed for 15 seconds and left overnight before centrifuging them. The residual rate of the samples was then analyzed by visual features, absorbance data, and DLS data. DLS samples were prepared by diluting the synthesized polymer micelle samples (100 times) and filtering through a 450nm filter, and representative size measurements were obtained using DLS. Samples for spectrophotometer UV-Vis measurements (Agilent) were diluted to obtain representative absorbance measurements. Preparation for visual characterization requires that samples be photographed individually in photo boxes and compared with stock samples.

[0517] UV-Vis spectra of representative composite particles in ethanol Fig.31 Representative UV-Vis spectra of composite particles in various solvents are shown in Figures A to F. Fig.31 This is shown in Figures G to I.

[0518] The DLS data of representative composite particles CS17, CS20, CS22 and CS04 are shown in Table 13, Table 14, Table 15 and Table 16, respectively.

[0519] Table 13-DSL data of CS17

[0520]

[0521] Table 14- DLS data of CS20

[0522]

[0523] Table 15-DSL data of CS22

[0524]

[0525] Table 16-DSL data of CS04

[0526]

[0527] The stability results in various solvents are summarized in Table 17. The satisfactory (S) / improved (I) criteria are based on visual inspection, UV-Vis absorbance, and DLS results of the comprehensive samples, where satisfactory samples are comparable to CS00, and improved samples have improved performance compared to CS00. Visual inspection compares the solution color of CS00 and the composite particles to determine the relative concentration of the dye. Compare the CS00 UV-Vis absorbance to the solution absorbance of the composite particles to determine the relative concentration of the dye. The DLS results of the composite particles indicate whether the particles are stable in the tested solvents. Based on visual inspection, UV-Vis absorbance, and DLS results, the composite particles of the present disclosure can better withstand solvent exposure than CS00, and show improvements over systems containing only free dyes, including CS04, CS17, CS19, CS20, CS22, CS28, CS29, CS31, CS33, CS34, and CS35.

[0528] Table 17 - Solvent Stability

[0529]

[0530] Example 21 Photobleaching of Composite Particles in Contact Lenses

[0531] Photobleaching is the photochemical alteration of a dye or fluorophore molecule such that the absorption spectrum of the compound is permanently altered or destroyed. Since normal wear of contact lenses may expose the lenses to a variety of UV conditions, it may be desirable for the composite particles incorporated into contact lenses to have a certain resistance to photobleaching. However, this is not an absolute criterion for composite particles used in contact lenses, since normal daily wear of contact lenses may only expose the lenses and composite particles to UV conditions that are much more gradual and significantly weaker than the photobleaching conditions used in this experiment.

[0532] Comparatives BC01, PH01 and PN01 were used. Composite particles CS28 to CS42 of the present disclosure were prepared and tested as described above. M2Dx prepolymer was prepared as described above. Two controls CS00 (free dye) and empty M2Dx polymer were also prepared as described above and used in this study.

[0533] The dried particles were resuspended in a stock of M2Dx and then the particles were diluted into another M2Dx solution until the secondary peak measured an absorbance of approximately 0.5 in the spectrophotometer. 12.5 μL of 2-hydroxy-2-methylpropiophenone (DAROCUR 1173) was then added as a photoinitiator to 3 mL of the M2Dx solution. The M2Dx was then polymerized in a UV reactor for 10 minutes and then stored in DI water. The spectrophotometer was blanked using M2Dx without dye or nanoparticles.

[0534] Photobleaching

[0535] The experiment used a UV reaction chamber to expose all samples to UV light (≈250nm). After exposure, each sample was measured using an Agilent spectrophotometer to determine the change in filter power. This was done at a series of time points every 1 minute. The samples were photobleached for a total of 5 minutes. The gel was measured after every 1 minute of photobleaching until 5 minutes were reached.

[0536] The UV-Vis absorption spectrum of a representative gel (containing CS35) is Fig.32 The photobleaching rates of each composite particle in the contact lens gel using the peak absorbance at 425 nm were found to follow second order kinetics. The photobleaching rates (k) of the second order kinetics are shown in Table 18, where a smaller k indicates a slower photobleaching rate. Most of the composite particles of the present disclosure exhibited slower photobleaching rates compared to the free dye (CS00) and comparative examples BC01 and PN01.

[0537] Table 18 - Photobleaching Rates

[0538]

[0539] Based on the secondary photobleaching rate, the composite particles of the present disclosure are resistant to photobleaching. These embodiments are CS28, CS29, CS30, CS31, CS32, CS33, CS34, CS35, CS36, CS37, CS38, CS39, CS40, CS41 and CS42. In particular, several composite particles of the present disclosure perform better than the control free dye CS00 in terms of photobleaching resistance, and show improvements to systems containing only free dyes. These embodiments are CS28, CS29, CS30, CS31, CS32, CS33, CS34, CS35, CS36, CS37, CS38, CS39, CS41 and CS42.

[0540] Furthermore, comparative example PN01 is not resistant to photobleaching.

[0541] Example 22 Shelf Life Storage Stability

[0542] Contact lenses for commercial use are usually immersed in phosphate buffered saline (PBS) and packaged in blister packs, sterilized and stored for a period of time. In this study, different composite particles incorporated in M2Dx gel were exposed to saline after autoclaving to simulate the storage conditions of sterilized contact lenses. This study followed the guidelines of Color Additive Petition established by the U.S. Food and Drug Administration to evaluate the migration of particles. The leaching of particles was determined by visual inspection and UV-Vis spectrometry. The saline used to hold the prototypes was measured to determine the presence of particles. Accelerated aging techniques were applied to reduce the saline exposure time. All test and control materials showed no leaching after 136.5 hours of saline exposure at 50°C, as no absorbance was measured at the dye peak wavelength at 425nm. In addition, no visual abnormalities were observed in either the gel or saline. Therefore, it can be concluded that saline exposure does not lead to particle migration and all test and control materials passed this shelf life study.

[0543] According to FDA regulations, to simulate daily wear contact lenses containing pigment additives, prototypes should be immersed in saline or PBS at 37 degrees Celsius for 14 days. In addition, 0.9% (by weight) saline or PBS and a surface area to volume ratio of 120 cm 2 Lens for 20mL extract (or 6cm 2 / mL) for migration studies.

[0544] To accelerate saline exposure, an FDA-approved accelerated aging technique was introduced. In this study, the prototypes were evaluated at a gel surface area to saline volume ratio of 6 cm 2 The test article was heat treated at 50 degrees Celsius for 136.5 hours. After the heat treatment, the saline was measured using a spectrophotometer to detect particle migration.

[0545] The stability of the nanoparticles will be evaluated using the following criteria:

[0546] 1. Aged particle-loaded contact lens prototypes should have the same / similar spectral and optical properties as the control

[0547] 2. The aged particle-loaded contact lens prototype should not have any obvious abnormalities (yellowing, turbidity, blackening, etc.)

[0548] 3. The spectrum of the saline solution used to extract the prototype should not contain signals from free dye or particles

[0549] 4. Free dye should not precipitate into saline.

[0550] Comparatives BC01, PH01 and PN01 were used. Composite particles CS28 to CS42 of the present disclosure were prepared and tested as described above. M2Dx prepolymer was prepared as described above. Two controls CS00 (free dye) and empty M2Dx polymer were also prepared as described above and used in this study.

[0551] The contact lens prototype was polymerized in a mold assembled by sandwiching an aluminum frame with a specified volume of 1 mL using two glass slides. Before the mold was assembled, an oil-based release agent was sprayed onto the frame and the glass slide as a release agent. The mold was placed in a plastic bag and pressure was applied to the glass slide using 4 clamps to avoid leakage. Once the spectral measurement was completed, 10 μl of the photoinitiator 2-hydroxy-2-methylpropiophenone (Darocure 1173) was immediately added to the M2Dx solution containing particles. The solution was then injected into the mold through the inlet using a 3 mL syringe. Once the solution was loaded, the bag was vacuum sealed using a vacuum sealer and then placed in a UV chamber. The M2Dx solution was UV cured in a plastic bag for 10 minutes. Once the curing process was completed, the gel was carefully transferred from the mold to a scintillation tube containing 20 mL of deionized water using round-tipped tweezers.

[0552] Autoclave

[0553] The prototypes were autoclaved in 5 mL of saline using an AMSCO Steris at 121 degrees Celsius and 108 kPa for 30 minutes. Composite particles CS28, CS29, CS30, CS31 and CS33 to CS41, as well as comparative examples BC01 and PH01 were autoclaved.

[0554] Accelerated aging

[0555] All 2cmx2cm prototypes were cut into 9 small pieces, so that the length, width and height of each piece were 0.67cm, 0.67cm and 0.1cm respectively. It made the total surface area of ​​each test piece reach 6.30cm 2 . In order to achieve 6cm 2 The surface area to volume ratio of 1.05 mL / mL was calculated by completely immersing the gel in 1.05 mL of saline. The prototype was then heated in a Thermo Scientific oven at 50 degrees Celsius for 136.5 hours. The required heating temperature and time were calculated using accelerated aging techniques based on Arrhenius theory. The samples were removed from the oven after the specified time and cooled to room temperature before spectral measurements.

[0556] Spectral measurement

[0557] The saline of the heated samples was measured using a spectrophotometer to identify the presence of particles or dye leached from the gel. The spectrophotometer was blanked with the saline used to hold the empty M2Dx and this saline was heat treated in the same manner as the other samples.

[0558] result

[0559] like Fig.33 As shown in, after aging for all test and control objects, no signal was observed in the visible light region of the saline solution used to contain the prototype. Due to surface defects (scratches) of the plastic disposable cuvette, some small peaks can be found at 368nm, 486nm, 637nm and 656nm. Visual inspection of the gel and saline after aging did not observe visual abnormalities (such as precipitation, yellowing and turbidity).

[0560] The spectroscopic data indicated that saline exposure did not result in migration of particles from the gel into solution, as no absorbance was measured at the peak wavelength of Zn(II)TPP at 425 nm. If free dye was leached from the gel, it would not be detected due to its hydrophobic nature, which renders it insoluble in saline. The saline was visually inspected for any solids, so it did not appear that any unencapsulated dye was released into the saline. No water-soluble material was leached from the gel, so no dye absorbance peak was detected at 425 nm by the spectrophotometer.

[0561] All granules have been shown to be storage stable according to the standards set by the FDA.

[0562] Example 23 Code name of the composite particle embodiment of the present disclosure

[0563] Table 19 shows a list of embodiments of composite particles of the present disclosure.

[0564] Table 19 - List and code names of composite particles

[0565]

[0566]

[0567]

[0568]

[0569]

[0570]

[0571] While the disclosure has been described with reference to what are presently considered to be the preferred embodiments, it should be understood that the invention is not limited to the disclosed embodiments, but rather is intended to cover various modifications and equivalent arrangements included within the spirit and scope of the appended claims.

[0572] All publications, patents, and patent applications are herein incorporated by reference in their entirety to the same extent as if each individual publication, patent, or patent application was specifically and individually indicated to be incorporated by reference in its entirety.

Claims

1. Use of one or more composite particles as a filter in a contact lens, the one or more composite particles comprising: Hydrophobic dyes; and an amphiphilic block copolymer encapsulating the hydrophobic dye, The hydrophobic dye has an absorbance in the range of ultraviolet to infrared regions of the electromagnetic spectrum, wherein the composite particles are substantially solvent-free, and The hydrophobic dye is selected from one or more combinations of coumarin, rhodamine, cyanine, porphyrin, phthalocyanine, anthraquinone, BODIPY, AzaBODIPY, carotenoids, 2-(2'hydroxy-5'-methacryloyloxyethylphenyl)-2H-benzotriazole, vitamin E, perylene, and p-quaterphenyl.

2. The use according to claim 1, wherein the amphiphilic block copolymer is crosslinked.

3. The use according to claim 1, wherein the hydrophobic dye is a laser dye or an absorbing dye.

4. The use according to claim 1, wherein the hydrophobic dye has absorbance in a combination of one or more selected from the group consisting of UV region, visible light region, and infrared region.

5. The use according to claim 1, wherein the hydrophobic dye has absorbance in a combination of one or more selected from the group consisting of a blue light region, a green light region, and a red light region.

6. The method according to claim 1, wherein the hydrophobic dye is selected from the group consisting of 1,3,5,7-tetramethyl-8-(4-hydroxyphenyl) BODIPY, 1,7-(di-4-N,N-dimethylaminophenyl)-3,5-(di-4-bromophenyl) AZABODIPY, 2,3,7,8,12,13,17,18-(octabromo)-5,10,15,20-(tetraphenyl) porphyrin, Zn(II) 5,10,15,20-tetraphenyl-21H,23H-porphyrin (Zn(II)TPP), Zn(II) 2,9,16,23-(tetranitro) phthalocyanine, coumarin 153, β-carotene, and one or more combinations thereof in oxyvanadium 2,3-naphthalocyanine.

7. The use according to claim 6, wherein the hydrophobic dye is Zn(II)5,10,15,20-tetraphenyl-21H,23H-porphyrin (Zn(II)TPP).

8. The use according to claim 1, wherein the amphiphilic block copolymer is biocompatible.

9. The use according to claim 1, wherein the amphiphilic block copolymer is a diblock copolymer or a triblock copolymer.

10. The use according to claim 9, wherein the amphiphilic block copolymer is a diblock copolymer.

11. The use according to claim 1, wherein the amphiphilic block copolymer is a combination of one or more of a poly(alkyl acrylate)-based copolymer, a poly(alkyl methacrylate)-based copolymer, a poly(acrylic acid)-based copolymer, a poly(N-isopropylacrylamide)-based copolymer, a poly(ethylene glycol)-based copolymer, a poly(methyleneindan)-based copolymer, a poly(siloxane)-based copolymer, a poly(styrene)-based copolymer, a substituted poly(styrene)-based copolymer, a poly(vinylpyridine)-based copolymer, a poly(vinyl alcohol)-based copolymer, a poly(alkyl acrylic acid)-based copolymer, a poly(alkylene oxide)-based copolymer, a poly(olefin)-based copolymer, a poly(alkylene oxide diacrylate)-based copolymer, and a poly(butylene glycol diacrylate)-based copolymer.

12. The use according to claim 1, wherein the amphiphilic block copolymer is a combination of one or more of a poly(alkyl acrylate)-based copolymer, a poly(alkyl methacrylate)-based copolymer, a poly(acrylic acid)-based copolymer, a poly(methacrylic acid)-based copolymer, a poly(olefin)-based copolymer, a poly(ethylene glycol)-based copolymer, a poly(siloxane)-based copolymer, a poly(styrene)-based copolymer, and a poly(vinyl alcohol)-based copolymer.

13. The use according to claim 1, wherein the amphiphilic block copolymer is a combination of one or more of a poly(methacrylic acid)-based copolymer, a poly(diene)-based copolymer, and a poly(dialkylsiloxane)-based copolymer.

14. The use according to claim 1, wherein the amphiphilic block copolymer is a combination of one or more of a copolymer based on poly(methyl acrylate), a copolymer based on poly(n-butyl acrylate), a copolymer based on poly(methyl methacrylate), a copolymer based on poly(tert-butyl methacrylate), a copolymer based on poly(acrylic acid), a copolymer based on poly(methacrylic acid), a copolymer based on poly(1,2-butadiene), a copolymer based on poly(1,4-butadiene), a copolymer based on poly(styrene), a copolymer based on poly(dimethylsiloxane), a copolymer based on poly(vinyl alcohol), and a copolymer based on poly(propylene oxide).

15. The use according to claim 1, wherein the amphiphilic block copolymer is selected from the group consisting of poly(1,2-butadiene)-b-poly(acrylic acid), poly(1,2-butadiene)-b-poly(methacrylic acid), poly(1,2-butadiene)-b-poly(methyl methacrylate), poly(1,2-butadiene-co-1,4-butadiene)-b-poly(acrylic acid), poly(1,2-butadiene-co-1,4-butadiene)-b-poly(methacrylic acid), poly(1,4-butadiene)-b-poly(acrylic acid), poly(1 ,4-butadiene)-b-poly(methacrylic acid), poly(dimethylsiloxane)-b-poly(acrylic acid), poly(dimethylsiloxane)-b-poly(ethylene oxide), poly(dimethylsiloxane)-b-poly(methacrylic acid), poly(dimethylsiloxane)-b-poly(n-butyl acrylate), poly(ethylene oxide)-b-poly(butadiene), poly(ethylene oxide)-b-poly(methyl methacrylate), poly(ethylene oxide)-b-poly(n-butyl acrylate), poly(ethylene oxide)-b-poly(styrene), poly(epoxy ethane)-b-poly(tert-butyl methacrylate), poly(methyl methacrylate)-b-poly(acrylic acid), poly(methyl methacrylate)-b-poly(dimethylsiloxane), poly(methyl methacrylate)-b-poly(methacrylic acid), poly(methyl methacrylate)-b-poly(styrene), poly(n-butyl acrylate)-b-poly(acrylic acid), poly(propylene oxide)-b-poly(butadiene), poly(propylene oxide)-b-poly(dimethylsiloxane), poly(propylene oxide)-b-poly(methyl methacrylate), A combination of one or more of poly(propylene oxide)-b-poly(n-butyl acrylate), poly(propylene oxide)-b-poly(styrene), poly(propylene oxide)-b-poly(tert-butyl methacrylate), poly(vinyl alcohol)-b-poly(butadiene), poly(vinyl alcohol)-b-poly(dimethylsiloxane), poly(vinyl alcohol)-b-poly(methyl methacrylate), poly(vinyl alcohol)-b-poly(n-butyl acrylate), poly(vinyl alcohol)-b-poly(styrene), and poly(vinyl alcohol)-b-poly(tert-butyl methacrylate).

16. The use according to claim 1, wherein the amphiphilic block copolymer is selected from the group consisting of one or more combinations of poly(1,2-butadiene)-b-poly(ethylene oxide), poly(1,2-butadiene-co-1,4-butadiene)-b-poly(ethylene oxide), poly(1,4-butadiene)-b-poly(ethylene oxide), poly(1,2-butadiene)-b-poly(vinyl alcohol), poly(1,2-butadiene-co-1,4-butadiene)-b-poly(vinyl alcohol), poly(1,4-butadiene)-b-poly(vinyl alcohol), poly(ethylene oxide)-b-poly(dimethylsiloxane), and poly(methyl methacrylate)-b-poly(ethylene oxide).

17. The use according to claim 1, wherein the amphiphilic block copolymer is selected from poly(1,2-butadiene) 15000 -b-Poly(acrylic acid) 6500 , poly(1,4-butadiene) 9000 -b-Poly(acrylic acid) 3500 , poly(dimethylsiloxane) 5000 -b-Poly(ethylene oxide) 2100 , poly(dimethylsiloxane) 8000 -b-Poly(acrylic acid) 8000 , poly(methyl methacrylate) 3000 -b-Poly(ethylene oxide) 3000 , poly(methyl methacrylate) 7400 -b-Poly(acrylic acid) 24300 , Poly(n-butyl acrylate) 7500 -b-Poly(acrylic acid) 5500 , poly(styrene) 1300 -b-Poly(ethylene oxide) 5600 , poly(vinyl alcohol) 2300 -b-Poly(methyl methacrylate) 25000 , poly(vinyl alcohol) 2500 -b-Poly(styrene) 12500 A combination of one or more of .

18. The use according to claim 1, wherein the amphiphilic block copolymer is end-functionalized.

19. The use according to claim 1, wherein the amphiphilic block copolymer is acrylate-terminated and / or methacrylate-terminated.

20. The use according to claim 1, wherein the number average molecular weight (M) of each block of the amphiphilic block copolymer is n ) are independently 250 to 100000, 1300 to 31500 or 2000 to 8000.

21. The use according to claim 1, wherein The hydrophobic block M of the amphiphilic block copolymer n M with hydrophilic block n The ratio is 0.02 to 128, 0.05 to 20, 0.23 to 10.9, 0.33 to 3, 0.02 to 0.50, 0.5 to 1, 1 to 5, 5 to 20, 20 to 50, or 50 to 128.

22. The use according to claim 1, wherein the amphiphilic block copolymer is crosslinked using a crosslinking method selected from the group consisting of dialdehyde crosslinking, diamine crosslinking, diol crosslinking, ester crosslinking, free radical initiated olefin polymerization, quaternary ammonium crosslinking, silane crosslinking, trialdehyde crosslinking, triamine crosslinking, triol crosslinking, and urethane crosslinking.

23. The use according to claim 22, wherein the silane crosslinking is carried out using a silane selected from a combination of one or more of monoalkyl silicate, dialkyl silicate, trialkyl silicate, and tetraalkoxy orthosilicate.

24. The use according to claim 23, wherein the tetraalkoxy orthosilicate is tetramethyl orthosilicate (TMOS) and / or tetraethyl orthosilicate (TEOS).

25. The use according to claim 22, wherein the free radical initiated olefin polymerization is initiated with a thermally and / or photoactivated free radical initiator.

26. Use according to claim 25, wherein the free radical initiator is a nitrile-based initiator and / or a peroxide-based initiator.

27. The method according to claim 25, wherein the free radical initiator is selected from azobisisobutyronitrile (AIBN), diisopropyl peroxydicarbonate (IPP), benzoyl peroxide (BPO), 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methylpropiophenone, trimethylolpropane tris(3-mercaptopropionate) and a combination of one or more thereof.

28. The use according to claim 22, wherein the amphiphilic block copolymer is crosslinked using silane crosslinking and free radical initiated olefin polymerization.

29. The use according to claim 28, wherein the amphiphilic block copolymer is crosslinked using TEOS and AIBN.

30. The use according to claim 1, wherein the amphiphilic block copolymer is selected from the group consisting of poly(1,2-butadiene)-b-poly(acrylic acid) crosslinked with AIBN, poly(1,2-butadiene)-b-poly(acrylic acid) crosslinked with fumed silica, poly(1,2-butadiene)-b-poly(acrylic acid) crosslinked with TEOS, poly(1,2-butadiene)-b-poly(acrylic acid) crosslinked with TEOS and AIBN, poly(1,4-butadiene)-b-poly(acrylic acid) crosslinked with AIBN, poly(1,4-butadiene)-b-poly(acrylic acid) crosslinked with TEOS, poly(1,4-butadiene)-b-poly(acrylic acid) crosslinked with TEOS and AIBN, The invention also comprises a combination of one or more of poly(dimethylsiloxane)-b-poly(acrylic acid) cross-linked with TEOS, poly(dimethylsiloxane)-b-poly(ethylene oxide) cross-linked with TEOS, poly(methyl methacrylate)-b-poly(acrylic acid) cross-linked with TEOS, poly(methyl methacrylate)-b-poly(ethylene oxide) cross-linked with TEOS, uncross-linked poly(methyl methacrylate)-b-poly(ethylene oxide), poly(n-butyl acrylate)-b-poly(acrylic acid) cross-linked with TEOS, poly(styrene)-b-poly(ethylene oxide) cross-linked with TEOS, poly(vinyl alcohol)-b-poly(methyl methacrylate) cross-linked with TEOS, and poly(vinyl alcohol)-b-poly(styrene) cross-linked with TEOS.

31. The use according to claim 1, wherein the amphiphilic block copolymer is selected from poly(1,2-butadiene) crosslinked with AIBN 15000 -b-Poly(acrylic acid) 6500 , poly(1,2-butadiene) cross-linked with fumed silica 15000 -b-Poly(acrylic acid) 6500 , Poly(1,2-butadiene) cross-linked with TEOS 15000 -b-Poly(acrylic acid) 6500 , Poly(1,2-butadiene) cross-linked with TEOS and AIBN 15000 -b-Poly(acrylic acid) 6500 , Poly(1,4-butadiene) cross-linked with AIBN 9000 -b-Poly(acrylic acid) 3500 , Poly(1,4-butadiene) cross-linked with TEOS 9000 -b-Poly(acrylic acid) 3500 , Poly(1,4-butadiene) cross-linked with TEOS and AIBN 9000 -b-Poly(acrylic acid) 3500 , Poly(dimethylsiloxane) cross-linked with TEOS 5000 -b-Poly(ethylene oxide) 2100 , Poly(dimethylsiloxane) cross-linked with TEOS 8000 -b-Poly(acrylic acid) 8000 , poly(methyl methacrylate) cross-linked with TEOS 3000 -b-Poly(ethylene oxide) 3000 , uncrosslinked poly(methyl methacrylate) 3000 -b-Poly(ethylene oxide) 3000 , poly(methyl methacrylate) cross-linked with TEOS 7400 -b-Poly(acrylic acid) 24300 , Poly(n-butyl acrylate) cross-linked with TEOS 7500 -b-Poly(acrylic acid) 5500 , poly(styrene) cross-linked with TEOS 1300 -b-Poly(ethylene oxide) 5600 , poly(vinyl alcohol) cross-linked with TEOS 2300 -b-Poly(methyl methacrylate) 25000 , poly(vinyl alcohol) cross-linked with TEOS 2500 -b-Poly(styrene) 12500 A combination of one or more of .

32. The use according to claim 1, wherein the amphiphilic block copolymer is selected from the group consisting of uncrosslinked poly(methyl methacrylate)-b-poly(ethylene oxide), poly(dimethylsiloxane)-b-poly(acrylic acid) crosslinked with TEOS, poly(methyl methacrylate)-b-poly(acrylic acid) crosslinked with TEOS, poly(1,2-butadiene)-b-poly(acrylic acid) crosslinked with TEOS, poly(1,4-butadiene)-b-poly(acrylic acid) crosslinked with TEOS, poly(dimethylsiloxane)-b-poly(ethylene oxide) crosslinked with TEOS, poly(vinyl alcohol)-b-poly(ethylene oxide) crosslinked with TEOS. ), poly(styrene)-b-poly(ethylene oxide) cross-linked with TEOS, poly(n-butyl acrylate)-b-poly(acrylic acid) cross-linked with TEOS, poly(1,2-butadiene)-b-poly(acrylic acid) cross-linked with AIBN, poly(1,4-butadiene)-b-poly(acrylic acid) cross-linked with AIBN, poly(1,2-butadiene)-b-poly(acrylic acid) cross-linked with TEOS and AIBN, poly(1,4-butadiene)-b-poly(acrylic acid) cross-linked with TEOS and AIBN, and a combination of one or more of poly(1,2-butadiene)-b-poly(acrylic acid) cross-linked with fumed silica.

33. The use according to claim 1, wherein the amphiphilic block copolymer is selected from uncrosslinked poly(methyl methacrylate) 3000 -b-Poly(ethylene oxide) 3000 , poly(methyl methacrylate) cross-linked with TEOS 3000 -b-Poly(ethylene oxide) 3000 , Poly(dimethylsiloxane) cross-linked with TEOS 8000 -b-Poly(acrylic acid) 8000 , poly(methyl methacrylate) cross-linked with TEOS 7400 -b-Poly(acrylic acid) 24300 , Poly(1,2-butadiene) cross-linked with TEOS 15000 -b-Poly(acrylic acid) 6500 , Poly(1,4-butadiene) cross-linked with TEOS 9000 -b-Poly(acrylic acid) 3500 , poly(1,2-butadiene) cross-linked with fumed silica 15000 -b-Poly(acrylic acid) 6500 , Poly(dimethylsiloxane) cross-linked with TEOS 5000 -b-Poly(ethylene oxide) 2100 , poly(vinyl alcohol) cross-linked with TEOS 2300 -b-Poly(ethylene oxide) 2100 , poly(styrene) cross-linked with TEOS1300 -b-Poly(ethylene oxide) 5600 , Poly(n-butyl acrylate) cross-linked with TEOS 7500 -b-Poly(acrylic acid) 5500 , Poly(1,2-butadiene) cross-linked with AIBN 15000 -b-Poly(acrylic acid) 6500 , Poly(1,4-butadiene) cross-linked with AIBN 9000 -b-Poly(acrylic acid) 3500 , Poly(1,2-butadiene) cross-linked with TEOS and AIBN 15000 -b-Poly(acrylic acid) 6500 , Poly(1,4-butadiene) cross-linked with TEOS and AIBN 9000 -b-Poly(acrylic acid) 3500 A combination of one or more of .

34. The use according to claim 1, wherein the composite particles have a diameter in the nanometer to micrometer range.

35. Use according to claim 34, wherein the composite particles have a diameter of from 1 nm to 600 nm.

36. The use according to claim 34, wherein the diameter of the composite particles is 30 nm to 100 nm.

37. The use according to claim 34, wherein the diameter of the composite particles is 40 nm to 60 nm.

38. The use according to claim 34, wherein the composite particles have a diameter of about 50 nm.

39. The use according to claim 1, wherein the amphiphilic block copolymer encapsulates the hydrophobic dye in the form of micelles.

40. The use according to claim 1, wherein the composite particles have a thermal conductivity of 12.8 mW / cm 2 The UV-Vis absorption spectrum was essentially unchanged after 30 min of UV exposure.

41. The use according to claim 1, wherein the composite particles are heated to 12.8 mW / cm 2 The maximum UV-Vis absorbance after 30 minutes of UV exposure was 12.8 mW / cm 2 The absorbance of the at least one embodiment of the present invention is at least 50%, at least 60%, at least 70%, at least 80% or at least 90% of the maximum UV-Vis absorbance before UV exposure.

42. The use according to claim 1, wherein the composite particles are heated to 12.8 mW / cm 2The UV-Vis spectrum after photobleaching is substantially unchanged after UV exposure at 250 nm for about 1 minute, about 3 minutes, about 5 minutes, about 10 minutes, or about 15 minutes.

43. The use according to claim 1, wherein the maximum UV-Vis absorbance of the composite particles after photobleaching by UV for 1 minute, about 3 minutes, about 5 minutes, about 10 minutes or about 15 minutes is 12.8 mW / cm at 250 nm. 2 At least 50%, at least 60%, at least 70%, at least 80% or at least 90% of the maximum UV-Vis absorbance prior to UV exposure.

44. The use according to claim 1, wherein the ionization temperature is 10000 W / m2 at 250 nm. 2 After UV exposure for 1 minute, about 3 minutes, about 5 minutes, about 10 minutes or about 15 minutes for photobleaching, the change in the UV-Vis transmission spectrum of the composite particles is less than 80%, less than 70%, less than 60%, less than 50% or less than 40%.

45. The use according to claim 1, wherein the maximum UV-Vis absorbance of the composite particles in water, THF or a mixture thereof after heating at about 60°C, about 70°C, about 80°C, about 90°C or about 100°C for about 1 hour, about 3 hours, about 5 hours, about 8 hours, about 10 hours, about 12 hours, about 18 hours, about 24 hours or about 30 hours is at least 50%, at least 60%, at least 70%, at least 80% or at least 90% of the maximum UV-Vis absorbance before heating.

46. ​​The use according to claim 1, wherein the UV-Vis absorption spectrum of the composite particles is substantially unchanged after high pressure sterilization in an aqueous solution at about 121°C and 108 kPa.

47. The use according to claim 1, wherein after autoclaving in aqueous solution at about 121°C, 108 kPa, the maximum UV-Vis absorbance of the composite particles is at least 50%, at least 60%, at least 70%, at least 80% or at least 90% of the maximum UV-Vis absorbance before autoclaving.

48. The use according to claim 1, wherein the UV-Vis absorption spectrum of the composite particles is substantially unchanged after ethanol washing for about 1 hour with about 25% v / v, about 50% v / v, about 75% v / v or about 95% v / v ethanol in water.

49. The use according to claim 1, wherein the maximum UV-Vis absorbance of the composite particles after ethanol washing for about 1 hour with about 25% v / v, about 50% v / v, about 75% v / v or about 95% v / v ethanol in water is at least 50%, at least 60%, at least 70%, at least 80% or at least 90% of the maximum UV-Vis absorbance before ethanol washing.

50. The use of claim 1, wherein the composite particle is stable when stored in normal saline at 50°C for at least one day, at least three days, at least four days, at least five days, at least 125 hours, at least 130 hours, or at least 136 hours.

51. The use according to claim 1, wherein the UV-Vis absorption spectrum of the composite particles is substantially unchanged after storage in 50°C physiological saline for at least one day, at least three days, at least four days, at least five days, at least 125 hours, at least 130 hours or at least 136 hours.

52. The use according to claim 1, wherein the maximum UV-Vis absorbance of the composite particles after storage in 50°C normal saline for at least one day, at least three days, at least four days, at least five days, at least 125 hours, at least 130 hours or at least 136 hours is at least 50%, at least 60%, at least 70%, at least 80% or at least 90% of the maximum UV-Vis absorbance before storage.

53. The use according to claim 1, wherein the composite particles have an energy density of 12.8 mW / cm at 250 nm. 2 The change in maximum UV-Vis absorbance after about 1 minute, about 3 minutes, about 5 minutes, about 10 minutes, or about 15 minutes of UV exposure for photobleaching is less than the change in maximum UV-Vis absorbance of the hydrophobic dye alone at 250 nm after about 1 minute, about 3 minutes, about 5 minutes, about 10 minutes, or about 15 minutes of UV exposure for photobleaching.

54. The use according to claim 1, wherein the composite particles have an energy density of 12.8 mW / cm at 250 nm. 2 The change in maximum UV-Vis transmittance after UV exposure for photobleaching for about 1 minute, about 3 minutes, about 5 minutes, about 10 minutes, or about 15 minutes is less than the change in maximum UV-Vis transmittance of the hydrophobic dye alone after UV exposure for photobleaching at 250 nm for about 1 minute, about 3 minutes, about 5 minutes, about 10 minutes, or about 15 minutes, respectively.

55. The use according to claim 1, wherein the change in maximum UV-Vis absorbance of the composite particle after heating at about 60°C, about 70°C, about 80°C, about 90°C or about 100°C for about 1 hour, about 3 hours, about 5 hours, about 8 hours, about 10 hours, about 12 hours or about 18 hours is less than the change in maximum UV-Vis absorbance of the hydrophobic dye after heating at about 60°C, about 70°C, about 80°C, about 90°C or about 100°C for about 1 hour, about 3 hours, about 5 hours, about 8 hours, about 10 hours, about 12 hours or about 18 hours, respectively.

56. The use of claim 1, wherein the change in maximum UV-Vis absorbance of the composite particles after autoclaving in aqueous solution at about 121°C, 108 kPa is less than the change in maximum UV-Vis absorbance of the hydrophobic dye after autoclaving in aqueous solution at 121°C, 108 kPa.

57. The use according to claim 1, wherein the change in the maximum UV-Vis absorbance of the composite particles after storage in 50°C saline for at least one day, at least three days, at least four days, at least five days, at least 125 hours, at least 130 hours or at least 136 hours is less than the change in the maximum UV-Vis absorbance of the hydrophobic dye after storage in 50°C saline for at least one day, at least three days, at least four days, at least five days, at least 125 hours, at least 130 hours or at least 136 hours.

58. The use according to claim 1, wherein the contact lens is hydrogel based.

59. The use according to claim 1, wherein the contact lens is silicone hydrogel based.

60. The use according to claim 1, wherein the filter selectively blocks optical radiation.

61. The use according to claim 60, wherein the light radiation is selected from a combination of one or more of infrared light, UV light, and visible light.

62. The use according to claim 60, wherein the light radiation is selected from a combination of one or more of blue light, green light, and red light.

63. The use according to claim 60, wherein the light radiation is UV light and / or blue light.

64. The use according to claim 1, wherein substantially no leaching of the composite particles from the contact lens is observed over time, exposure to organic solvents, or exposure to temperature changes.

65. A contact lens comprising one or more composite particles as defined in any one of claims 1 to 57.

66. The contact lens of claim 65, wherein the contact lens is hydrogel based.

67. The contact lens of claim 65, wherein the contact lens is silicone hydrogel based.

68. The contact lens of claim 66, wherein the hydrogel is biocompatible and / or suitable for use in an animal subject.

69. The contact lens of claim 67, wherein the silicone hydrogel is biocompatible and / or suitable for use in an animal subject.

70. The contact lens of claim 68 or 69, wherein the animal subject is a mammal.

71. The contact lens of claim 70, wherein the mammal is a human.

72. The contact lens of claim 65, wherein the contact lens is provided by 12.8 mW / cm at 250 nm. 2 The maximum UV-Vis absorbance of the contact lens after about 1 minute, about 3 minutes, about 5 minutes, about 10 minutes, or about 15 minutes of UV photobleaching is 12.8 mW / cm at 250 nm. 2 At least 50%, at least 60%, at least 70%, at least 80% or at least 90% of the maximum UV-Vis absorbance prior to UV exposure.

73. The contact lens of claim 65, wherein the contact lens is provided by 12.8 mW / cm at 250 nm. 2 The change in the UV-Vis transmission spectrum after about 1 minute, about 3 minutes, about 5 minutes, about 10 minutes, or about 15 minutes of UV exposure for photobleaching is less than 80%, less than 70%, less than 60%, less than 50%, or less than 40%.

74. The contact lens of claim 65, wherein the UV-Vis absorption spectrum of the contact lens is substantially unchanged after autoclaving in aqueous solution at about 121°C, 108 kPa.

75. The contact lens of claim 65, wherein the UV-Vis absorption spectrum of the contact lens is substantially unchanged after ethanol washing for about 1 hour with about 25% v / v, about 50% v / v, about 75% v / v, or about 95% v / v ethanol in water.

76. The contact lens of claim 65, wherein the contact lens has a maximum UV-Vis absorbance after ethanol washing for about 1 hour with about 25% v / v, about 50% v / v, about 75% v / v, or about 95% v / v ethanol in water that is at least 50%, at least 60%, at least 70%, at least 80%, or at least 90% of the maximum UV-Vis absorbance before the ethanol wash.

77. The contact lens of claim 65, wherein the contact lens is stable when stored in normal saline at 50°C for at least one day, at least three days, at least four days, at least five days, at least 125 hours, at least 130 hours, or at least 136 hours.

78. The contact lens of claim 65, wherein the UV-Vis absorption spectrum of the contact lens is substantially unchanged after storage in 50°C saline for at least one day, at least three days, at least four days, at least five days, at least 125 hours, at least 130 hours, or at least 136 hours.

79. The contact lens of claim 65, wherein the maximum UV-Vis absorbance of the contact lens after storage in 50°C saline for at least one day, at least three days, at least four days, at least five days, at least 125 hours, at least 130 hours, or at least 136 hours is at least 50%, at least 60%, at least 70%, at least 80%, or at least 90% of the maximum UV-Vis absorbance before storage.

80. A method of filtering light in a contact lens comprising selectively blocking optical radiation using one or more composite particles as defined in any one of claims 1 to 57.

81. The method of claim 80, wherein the optical radiation is selected from a combination of one or more of infrared light, UV light, and visible light.

82. The method of claim 80, wherein the light radiation is selected from a combination of one or more of blue light, red light, and green light.

83. The method of claim 80, wherein the optical radiation is UV light and / or blue light.